Pretreatment compositions bonded to metal substrates and methods of making the same
Graft copolymer pretreatment compositions address multiple surface issues of aluminum alloys by enhancing corrosion resistance, adhesive durability, and weldability, improving performance in automotive and industrial applications.
Patent Information
- Application Number
- JP2024179290
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-06-10
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Aluminum alloys face issues with corrosion, poor adhesive durability, uneven coatings, and poor weldability, necessitating pretreatment compositions that address multiple surface-related problems simultaneously.
The use of graft copolymer pretreatment compositions comprising a polymer backbone with surface bond moieties and functional moieties that provide corrosion resistance, adhesion promotion, lubrication, and weldability through crosslinking agents, applied via methods like roll coating or dip coating.
The compositions enhance corrosion resistance, improve adhesive durability, provide uniform coatings, and improve weldability of aluminum alloys, leading to better performance in automotive and industrial applications.
Smart Images

Figure 2025010164000016 
Figure 2025010164000017 
Figure 2025010164000018
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to and the benefit of U.S. Provisional Patent Application No. 62 / 705,094, filed June 10, 2020, which is incorporated by reference in its entirety.
[0002] The present disclosure relates to the fields of materials science, materials chemistry, surface science, metal manufacturing, aluminum alloys, and aluminum manufacturing. Disclosed herein are compositions and methods that can be used in automotive, transportation, electronics, industrial, and other applications. The compositions and methods disclosed herein are particularly suited for automotive use. [Background technology]
[0003] Aluminum alloys are often used in environments that may adversely affect the surface, or at least a portion of the surface, of the aluminum alloy. As such, aluminum alloys may be susceptible to corrosion, have poor adhesion durability, difficulty in separating stacked aluminum alloy products, non-uniform coatings, and poor weldability and / or weld durability. Many pretreatment compositions provide functionality that addresses a single surface-related problem. Thus, a pretreatment composition that incorporates multiple surface functionalities is desirable. Summary of the Invention
[0004] The embodiments of the invention encompassed are defined by the claims, not this summary. This summary is a high-level overview of various aspects of the invention and introduces some of the concepts that are further described in the Detailed Description section below. This summary is not intended to identify key or essential features of the claimed subject matter, nor is it intended to be used alone to determine the scope of the claimed subject matter. The subject matter should be understood by reference to the entire specification, some or all of the drawings, and appropriate portions of the claims.
[0005] Described herein are graft copolymer pretreatment compositions comprising a polymer backbone, at least one surface binding or bonding moiety (e.g., anchor group) attached to the polymer backbone and configured to bond or join the polymer backbone to a first surface of a metal article, at least one functional moiety attached to the polymer backbone and configured to provide at least a first surface functionalization to the first surface of the metal article, and at least one second functional moiety attached to the polymer backbone and configured to provide at least a second surface functionalization to the first surface of the metal article, where the at least one functional moiety and the at least one second functional moiety provide a multi-functional surface coating.
[0006] In some examples, the polymer backbone comprises an acrylic class of linear polymer structures, a methacrylic class of linear polymer structures, a vinyl class of linear polymer structures, a diene class of linear polymer structures, a vinylidene class of linear polymer structures, or any combination thereof. For example, the polymer backbone can be poly(methyl methacrylate), poly(ethyl methacrylate), poly(ethyl acrylate), polyacrylonitrile, polyethylene, polypropylene, polystyrene, poly(vinyl chloride), poly(vinyl acetate), poly(vinyl alcohol), polybutadiene, polyisoprene, polychloroprene, or any combination thereof.
[0007] In certain embodiments, at least one surface-bonding or joining moiety comprises a phosphonate group, a carboxyl group, a catechol group, or a trialkoxysilyl group. For example, the phosphonate group can be a poly(vinyl phosphonate). In addition, at least one functional moiety can comprise an adhesion promoter (e.g., a hydroxyl group, an amide group, a thiol group, an epoxide group, a vinyl group, a diol group, an adhesive composition, a covalent bond group, or an ionic bond group). In some cases, at least one functional moiety comprises a polymer side chain that provides a lubricating function (e.g., polyethylene glycol, polytetrahydrofuran, polyisobutene, polysilicone, or any combination thereof). In some further cases, at least one functional moiety comprises a humectant (e.g., polypropylene glycol, hexylene glycol, butylene glycol, lactic acid, sodium hexametaphosphate, glycerol, sorbitol, xylitol, maltitol, urea, or any combination thereof). In some examples, at least one functional moiety comprises a welding promoter.
[0008] In certain cases, at least one functional moiety includes a corrosion inhibitor (e.g., an inorganic corrosion inhibitor, an inorganic barrier type corrosion inhibitor, an organic corrosion inhibitor, an organic barrier type corrosion inhibitor, or any combination thereof). For example, the inorganic corrosion inhibitor can include a transition metal, a transition metal salt, a rare earth metal, or a rare earth metal salt. In some cases, the transition metal includes titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), zirconium (Zr), niobium (Nb), molybdenum (Mo), ruthenium (Ru), rhodium (Rh), palladium (Pd), silver (Ag), cadmium (Cd), hafnium (Hf), tantalum (Ta), tungsten (W), rhenium (Re), osmium (Os), iridium (Ir), platinum (Pt), or gold (Au) and / or a salt of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Cd, Hf, Ta, W, Re, Os, Ir, Pt, or Au. In particular examples, rare earth metals include cerium (Ce), scandium (Sc), yttrium (Y), lanthanum (La), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), or lutetium (Lu) and / or salts of Ce, Sc, Y, La, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, or Lu. In some embodiments, the corrosion inhibitor includes an organic corrosion inhibitor such as mercaptobenzothiazole, benzotriazole, salicylaldoxime, dithiooxamide, quinaldic acid, thioacetamide, or 8-hydroxyquinoline. In certain examples, the at least one second functional moiety includes an adhesion promoter, a polymeric side chain that provides a lubricating function, a humectant, a welding promoter, or a corrosion inhibitor.
[0009] In certain embodiments, the graft copolymer pretreatment composition is crosslinked with a crosslinking agent (e.g., a zirconium salt or a zirconium complex). Optionally, the crosslinking agent is an aqueous solution of a zirconium salt or a zirconium complex.
[0010] Also described herein are methods of pretreating at least a portion of a metal surface, comprising applying a graft copolymer pretreatment composition to at least a portion of the metal surface. In some cases, applying the graft copolymer pretreatment composition comprises solution coating at least a portion of the metal surface (e.g., roll coating, dip coating, enrobing, spin coating, or spray coating at least a portion of the metal surface).
[0011] Other objects and advantages will become apparent from the following non-limiting examples and detailed description of formulas. [Brief description of the drawings]
[0012] [Figure 1] 4 is a graph showing the thickness of a spin-coated film according to an embodiment described herein. [Diagram 2] 1 shows an atomic force microscope (AFM) image of a spin-coated thin film according to an embodiment described herein. [Diagram 3] 1 shows an atomic force microscope (AFM) image of a spin-coated and washed thin film according to an embodiment described herein. [Figure 4] 1 shows X-ray photoelectron spectroscopy (XPS) scans of thin films according to examples described herein. [Diagram 5] 1 shows X-ray photoelectron spectroscopy (XPS) scans of thin films according to examples described herein. [Figure 6] 1 shows X-ray photoelectron spectroscopy (XPS) scans of thin films according to examples described herein. [Figure 7] 1 shows the film thickness of a spin-coated sample of a cross-linked polymer film according to an embodiment described herein. [Figure 8]FIG. 2 is a schematic diagram showing a cross-linked graft copolymer layer applied to an aluminum surface forming a polymer gel using Zr as a cross-linker for the phosphonic acid groups, according to examples described herein. [Figure 9] 1 shows X-ray photoelectron spectroscopy (XPS) scans of thin films before and after crosslinking according to examples described herein. [Figure 10] 1 shows the zirconium content as determined by XPS and the corresponding tribological performance according to the examples described herein. [Figure 11] 1 shows the zirconium content as determined by XPS and the corresponding tribological performance according to the examples described herein. [Figure 12] 1 is a graph showing the coefficient of friction of thin films from cycle testing according to examples described herein. [Figure 13] 1 is a graph showing the coefficient of friction of thin films from cycle testing according to examples described herein. [Figure 14] 1 is a graph showing the coefficient of friction of thin films from cycle testing according to examples described herein. [Figure 15] 1 is a graph showing the coefficient of friction of thin films from cycle testing according to examples described herein. [Figure 16] 1 is a graph showing the coefficient of friction of thin films from cycle testing according to examples described herein. [Figure 17] 1 is a graph showing the coefficient of friction of thin films from cycle testing according to examples described herein. [Figure 18] 1 is a graph showing the coefficient of friction of thin films from cycle testing according to examples described herein. [Figure 19] 1 is a graph showing the coefficient of friction of thin films from cycle testing according to examples described herein. [Figure 20] 1 shows the tribological performance of a polymer gel layer depending on the amount of polymer applied, according to examples described herein. [Figure 21]1 shows the tribological performance of a polymer gel layer depending on the amount of polymer applied, according to examples described herein. [Figure 22] 1 shows the tribological performance of a polymer gel layer depending on the amount of polymer applied, according to examples described herein. [Figure 23] 1 shows film thickness as determined by ellipsometry and tribological performance under different storage conditions according to examples described herein. [Figure 24] 1 is a graph showing water and lubricant contact angles of thin films according to examples described herein. [Diagram 25] 1 is a graph showing the coefficient of friction of lubricated samples from cycle testing according to examples described herein. [Figure 26] 1 is a graph showing the coefficient of friction of lubricated samples from cycle testing according to examples described herein. [Figure 27] 1 is a graph showing the coefficient of friction of thin films from cycle testing according to examples described herein. [Figure 28] 1 is a graph showing the coefficient of friction of thin films from cycle testing according to examples described herein. [Figure 29] 1 is a graph showing the coefficient of friction of thin films from cycle testing according to examples described herein. [Diagram 30] 1 is a graph showing the coefficient of friction of thin films from cycle testing according to examples described herein. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Provided herein are graft copolymer pretreatment compositions that impart surface functionalization to metals, including alloys such as aluminum alloys. Also provided herein are metals (e.g., aluminum alloys) coated with the disclosed graft copolymer pretreatment compositions, along with methods of applying the disclosed graft copolymer pretreatment compositions to metals. As used herein, pretreatment refers to a surface modification that is applied to a surface, typically in the form of a solution or suspension, and converted into a layer via physical and / or chemical reaction. The pretreatment layer is applied before the metal is processed or used (e.g., before a molding process, before the metal is used in an outdoor environment, etc.). The pretreatment layer imparts properties and performance qualities that can be significantly different from the bulk of the metal or the metal surface. For example, the graft copolymer pretreatment compositions and methods described herein provide superior corrosion resistance to metal surfaces compared to non-pretreated metal surfaces. Additionally, the disclosed coatings and methods improve the corrosion resistance of metals (e.g., aluminum and aluminum alloys) when used under corrosive conditions, for example, in automotive structural and / or automotive body parts.
[0014] In some cases, the graft copolymer pretreatment compositions and methods described herein impart superior adhesive performance to metal surfaces as compared to non-pretreated metal surfaces. In certain aspects, the graft copolymer pretreatment compositions and methods described herein provide lubricity to metal surfaces as compared to non-pretreated metal surfaces. In some examples, the graft copolymer pretreatment compositions and methods described herein provide superior coating performance (e.g., enhanced moisture retention) to alloy surfaces as compared to non-pretreated metal surfaces. In certain cases, the graft copolymer pretreatment compositions and methods described herein improve the weldability and / or weld durability of metal surfaces as compared to non-pretreated metal surfaces. In certain aspects, the graft copolymer pretreatment compositions and methods described herein provide multi-functional surface coatings that impart at least one of lubricity, corrosion resistance, improved adhesive performance, improved coating performance, and / or improved weldability and / or weld durability.
[0015] Definitions and Explanations: As used herein, the terms "invention," "the invention," "this invention," and "the present invention" are intended to refer broadly to all of the subject matter of this patent application and the claims that follow. Statements containing these terms should be understood not to limit the subject matter described herein or to limit the meaning or scope of the claims that follow.
[0016] References are made herein to alloys identified by aluminum industry designations such as "series" or "6xxx." To understand the numbering systems most commonly used to name and identify aluminum and its alloys, please refer to "International Alloy Designations and Chemical Composition Limits for Wrought Aluminum and Wrought Aluminum Alloys" or "Registration Record of Aluminum Association Alloy Designations and Chemical Composition Limits for Aluminum Alloys in the Form of Castings and Ingot," both of which are published by the Aluminum Association.
[0017] As used herein, the meanings of "a," "an," or "the" include singular and plural referents unless the context clearly dictates otherwise.
[0018] As used herein, plate generally has a thickness of greater than about 15 mm. For example, plate can refer to an aluminum product having a thickness of greater than about 15 mm, greater than about 20 mm, greater than about 25 mm, greater than about 30 mm, greater than about 35 mm, greater than about 40 mm, greater than about 45 mm, greater than about 50 mm, greater than about 100 mm, or up to about 200 mm.
[0019] As used herein, a shade (also called a sheet plate) generally has a thickness of about 4 mm to about 15 mm. For example, the shade may be about 4 mm, about 5 mm, about 6 mm, about 7 mm, about 8 mm, about 9 mm, about 10 mm, about 11 mm, about 12 mm, about 13 mm, about 14 mm, or about 15 mm thick.
[0020] As used herein, sheet generally refers to an aluminum product having a thickness of less than about 4 mm. For example, the sheet may have a thickness of less than about 4 mm, less than about 3 mm, less than about 2 mm, less than about 1 mm, less than about 0.5 mm, less than about 0.3 mm, or less than about 0.1 mm.
[0021] In this application, reference is made to alloy tempers or tempers. For an understanding of the most commonly used alloy temper descriptions, please refer to "American National Standards (ANSI) H35 on Alloy and Temper Designation Systems". The F temper or temper refers to the aluminum alloy as produced. The O temper or temper refers to the aluminum alloy after annealing. The Hxx temper or temper, also referred to herein as the H temper, refers to an aluminum alloy that is not heat treatable after cold rolling, with or without heat treatment (e.g., annealing). Suitable H tempers include Hx1, Hx2, Hx3, Hx4, Hx5, Hx6, Hx7, Hx8, or Hx9 tempers. The T1 temper or temper refers to an aluminum alloy that has been cooled from hot working and naturally aged (e.g., at room temperature). The T2 temper or temper refers to an aluminum alloy that has been cooled from hot working, cold worked, and naturally aged. The T3 temper or temper refers to an aluminum alloy that has been solution heat treated, cold worked, and naturally aged. The T4 temper or temper refers to an aluminum alloy that has been solution heat treated and naturally aged. The T5 temper or temper refers to an aluminum alloy that has been cooled from hot working and artificially aged (at an elevated temperature). The T6x temper or temper refers to an aluminum alloy that has been solution heat treated and artificially aged. The T7 temper or temper refers to an aluminum alloy that has been solution heat treated and artificially overaged. The T8x temper or temper refers to an aluminum alloy that has been solution heat treated, cold worked, and artificially aged. The T9 temper or temper refers to an aluminum alloy that has been solution heat treated, artificially aged, and cold worked. The W temper or temper refers to an aluminum alloy after solution heat treatment.
[0022] As used herein, the meaning of "room temperature" can include a temperature of about 15°C to about 30°C, such as about 15°C, about 16°C, about 17°C, about 18°C, about 19°C, about 20°C, about 21°C, about 22°C, about 23°C, about 24°C, about 25°C, about 26°C, about 27°C, about 28°C, about 29°C, or about 30°C.
[0023] All ranges disclosed herein should be understood to encompass all endpoints and any and all subranges subsumed therein. For example, a stated range "1 to 10" should be considered to include every subrange between (and including) the minimum value of "1" and the maximum value of "10," i.e., every subrange beginning with a minimum value of 1 or more (e.g., 1 to 6.1) and ending with a maximum value of 10 or less (e.g., 5.5 to 10).
[0024] As used herein, the terms "cast metal product," "cast product," "cast aluminum alloy product," and the like, are intended to mean the same thing and refer to products produced by direct chill casting (including direct chill co-casting) or semi-continuous casting, continuous casting (including, for example, by use of a twin belt caster, twin roll caster, twin block caster, or any other continuous casting machine), electromagnetic casting, hot top casting, or any other casting method.
[0025] When used with a list of two or more items, the term "and / or" means that any one of the listed items can be used alone or in combination with one or more of the listed items. For example, the phrase "A and / or B" is intended to mean either or both of A and B, i.e., A alone, B alone, or a combination of A and B. The phrase "A, B, and / or C" is intended to mean A alone, B alone, C alone, a combination of A and B, a combination of A and C, a combination of B and C, or a combination of A, B, and C.
[0026] As used herein, the term "surface functionalization" refers to methods and compositions for modifying the surface properties and / or characteristics of a material to achieve desired surface properties, including, but not limited to, corrosion resistance, improved adhesion, uniform moisture retention, accelerated drying, any other desired surface property or characteristic, or any combination thereof.
[0027] As used herein, the acrylic class of linear polymer structures are formed by polymerizing functionalized and / or non-functionalized acrylate monomers (e.g., monomers having the structure -CH2=CHCOOR) into linear polymers; the methacrylic class of linear polymer structures are formed by polymerizing functionalized and / or non-functionalized methacrylate monomers (e.g., monomers having the structure -CH2=CCH3COOR) into linear polymers; the vinyl class of linear polymer structures are formed by polymerizing functionalized and / or non-functionalized vinyl monomers (e.g., monomers having the structure -CH2=CH-R) into linear polymers; the diene class of linear polymer structures are formed by polymerizing functionalized and / or non-functionalized diene monomers (e.g., monomers having the structure -CH2=CR-CR'=CH2) into linear polymers; and the vinylidene class of linear polymer structures are formed by polymerizing functionalized and / or non-functionalized vinylidene monomers (e.g., monomers having the structure -C=CRR') into linear polymers. In the above examples, R and R' are each independently selected from hydrogen, a functionalized or non-functionalized alkyl substituent, a functionalized or non-functionalized alkenyl substituent, a functionalized or non-functionalized alkynyl substituent, any suitable substituent described herein, or any suitable polymer side chain.
[0028] As used herein, the terms alkyl, alkenyl, and alkynyl include straight and branched chain monovalent substituents. Examples include methyl, ethyl, isobutyl, 3-butynyl, and the like. The range of these groups useful in the compositions and methods described herein includes C1-C 20 Alkyl, C2-C 20 Alkenyl, and C2-C 20 Further scope of these groups useful in the compositions and methods described herein include C1-C 12 Alkyl, C2-C 12 Alkenyl, C2-C 12Includes alkynyl, C1-C6 alkyl, C2-C6 alkenyl, C2-C6 alkynyl, C1-C4 alkyl, C2-C4 alkenyl, and C2-C4 alkynyl.
[0029] Heteroalkyl, heteroalkenyl, and heteroalkynyl are defined similarly to alkyl, alkenyl, and alkynyl, but may contain O, S, or N heteroatoms or combinations thereof in the backbone. The range of these groups useful in the compositions and methods described herein includes C1-C 20 Heteroalkyl, C2-C 20 Heteroalkenyl, and C2-C 20 A further scope of these groups useful in the compositions and methods described herein includes C1-C 12 Heteroalkyl, C2-C 12 Heteroalkenyl, C2-C 12 Includes heteroalkynyl, C1-C6 heteroalkyl, C2-C6 heteroalkenyl, C2-C6 heteroalkynyl, C1-C4 heteroalkyl, C2-C4 heteroalkenyl, and C2-C4 heteroalkynyl.
[0030] The terms cycloalkyl, cycloalkenyl, and cycloalkynyl include cyclic alkyl groups having a single ring or multiple condensed rings. Examples include cyclohexyl, cyclopentylethyl, and adamantanyl. The range of these groups useful in the compositions and methods described herein includes C 3- C 20 Cycloalkyl, C 3- C 20 Cycloalkenyl, and C 3- C 20 Further scope of these groups useful in the compositions and methods described herein include C5-C 12 Cycloalkyl, C5-C 12 Cycloalkenyl, C5-C 12 Includes cycloalkynyl, C5-C6 cycloalkyl, C5-C6 cycloalkenyl, and C5-C6 cycloalkynyl.
[0031] The terms heterocycloalkyl, heterocycloalkenyl, and heterocycloalkynyl are defined similarly to cycloalkyl, cycloalkenyl, and cycloalkynyl, but may contain O, S, or N heteroatoms or combinations thereof within the cyclic backbone. Scope of these groups useful in the compositions and methods described herein includes C 3- C 20 Heterocycloalkyl, C 3- C 20 Heterocycloalkenyl, and C 3- C 20 A further scope of these groups useful in the compositions and methods described herein includes C5-C 12 Heterocycloalkyl, C5-C 12 Heterocycloalkenyl, C5-C 12 Includes heterocycloalkynyl, C5-C6 heterocycloalkyl, C5-C6 heterocycloalkenyl, and C5-C6 heterocycloalkynyl.
[0032] The term hydroxyl as used herein is represented by the formula --OH.
[0033] Aryl molecules include, for example, cyclic hydrocarbons incorporating one or more planar sets of carbon atoms, usually six, connected by the same numbered delocalized electrons as in the case of alternating single and double covalent bonds. An example of an aryl molecule is benzene. Heteroaryl molecules include substitutions along the main ring atom chain, such as O, N, or S. Examples of heteroaryl molecules include furan, pyrrole, thiophene, imidazole, oxazole, pyridine, and pyrazine. Aryl and heteroaryl molecules can also include additional fused rings, such as benzofuran, indole, benzothiophene, naphthalene, anthracene, and quinoline. Unless otherwise specified, aryl and heteroaryl molecules can be attached at any position on the ring.
[0034] As used herein, the term "alkoxy" refers to an alkyl group bonded to the remainder of the molecule through an oxygen atom. As used herein, the term "aryloxy" refers to an aryl group bonded to the remainder of the molecule through an oxygen atom. Similarly, as used herein, the terms alkenyloxy, alkynyloxy, heteroalkyloxy, heteroalkenyloxy, heteroalkynyloxy, heteroaryloxy, cycloalkyloxy, and heterocycloalkyloxy are alkenyloxy, alkynyloxy, heteroalkyloxy, heteroalkenyloxy, heteroalkynyloxy, heteroaryloxy, cycloalkyloxy, and heterocycloalkyloxy groups, respectively, bonded to the remainder of the molecule through an oxygen atom.
[0035] As used herein, alkoxy, aryloxy, amino, alkyl, alkenyl, alkynyl, aryl, heteroalkyl, heteroalkenyl, heteroalkynyl, heteroaryl, cycloalkyl, or heterocycloalkyl molecules can be substituted or unsubstituted. As used herein, the term substituted includes the addition of an alkoxy, aryloxy, amino, alkyl, alkenyl, alkynyl, aryl, heteroalkyl, heteroalkenyl, heteroalkynyl, heteroaryl, cycloalkyl, or heterocycloalkyl group to the position attached to the backbone of the alkoxy, aryloxy, amino, alkyl, alkenyl, alkynyl, aryl, heteroalkyl, heteroalkenyl, heteroalkynyl, heteroaryl, cycloalkyl, or heterocycloalkyl group, for example, replacing hydrogen with one of these molecules. Examples of substituents include, but are not limited to, hydroxy, halide (e.g., fluoride, chloride, bromide, or iodide), and carboxyl groups. Conversely, as used herein, the term unsubstituted indicates that the alkoxy, aryloxy, amino, alkyl, alkenyl, alkynyl, aryl, heteroalkyl, heteroalkenyl, heteroalkynyl, heteroaryl, cycloalkyl, or heterocycloalkyl has a full complement of hydrogens, i.e., commensurate with its level of saturation, and has no substitution, such as, for example, straight chain decane (-(CH2)9-CH3).
[0036] The structures depicted herein include all enantiomers, diastereomers, and geometric (or conformational) forms of the structure; for example, the R and S configurations of each asymmetric center, cis and trans isomers, (Z) and (E) double bond isomers, and (Z) and (E) conformational isomers.
[0037] As used herein, the term "polymer" includes homopolymers and copolymers. Homopolymer means a polymer derived from a single polymerizable monomer. Copolymer means a polymer derived from two or more polymerizable monomers.
[0038] As used herein, a crosslinked polymer is defined by the presence of interchain bonds connecting two or more individual polymer chains. Crosslinked polymers can be permanently or temporarily crosslinked.
[0039] As used herein, a polymer gel is a substantially diluted cross-linked polymer. The polymer gel can be formed by adding a cross-linking agent or a small amount of a di-(or poly)functional monomer during the polymerization of the polymerizable monomer in the presence of a solvent. Alternatively, cross-linking can be achieved in a subsequent step of applying the cross-linking agent to a suitable polymer incorporating cross-linkable functional groups. The latter can be achieved after further processing of the uncross-linked polymer, including application as a thin film on a metal surface.
[0040] As used herein, a crosslinking agent is capable of linking two or more individual chains together by reacting with suitable functional groups in the polymer.
[0041] Pretreatment composition: Described herein in some examples are graft copolymer pretreatment compositions that are bonded to at least a portion of the surface of a metal product, including a metal alloy product, such as an aluminum alloy product. Although aluminum alloy products are described throughout the document, the methods and products apply to any metal. In some examples, the metal product may be aluminum, aluminum alloy, magnesium, magnesium-based materials, titanium, titanium-based materials, copper, copper-based materials, steel, steel-based materials, bronze, bronze-based materials, brass, brass-based materials, composite materials, sheets used in composite materials, or any other suitable metal or combination of materials. Metal products may include monolithic materials as well as non-monolithic materials, such as roll-bonded materials, clad materials, composite materials, or various other materials. In some examples, the metal product is a metal coil, metal strip, metal plate, metal sheet, metal billet, metal ingot, etc.
[0042] In some non-limiting examples, the graft copolymer pretreatment compositions described herein comprise a polymer backbone, a pendant moiety capable of binding or bonding the graft copolymer pretreatment composition to a metal surface (i.e., a surface-binding or bonding moiety), and at least one functional pendant moiety (i.e., a functional moiety) capable of imparting a functional pretreatment property to the metal surface. Polymer backbone
[0043] In some cases, the polymer backbone is an acrylic class linear polymer structure, a methacrylic class linear polymer structure, a vinyl class linear polymer structure, a diene class linear polymer structure, a vinylidene class linear polymer structure, or any combination thereof. For example, the polymer backbone can be poly(methacrylic acid), poly(methyl methacrylate), poly(ethyl methacrylate), poly(acrylic acid), poly(methyl acrylate), poly(ethyl acrylate), poly(butyl acrylate), polyacrylonitrile, polyethylene, polypropylene, polystyrene, poly(vinyl chloride), poly(vinyl acetate), poly(vinyl alcohol), polybutadiene, polyisoprene, polychloroprene, or any combination thereof.
[0044] In some cases, linear polymer structures can be prepared from vinyl-containing monomers to form the backbone according to Formula I below: [ka] In formula I, n ranges from 10 to 1000 (e.g., 15 to 750, 20 to 700, 25 to 650, 50 to 600, 100 to 500, or 200 to 400). Also in formula I, R includes a functional moiety capable of imparting functional pretreatment properties to the metal surface (e.g., the functional moiety can be a corrosion inhibitor, an adhesion promoter, a polymeric side chain that provides a lubricating function (i.e., a lubricant and / or a lubricating functional moiety), a humectant, and / or a weld promoter, as described below). Optionally, the functional moiety can include an ethylene oxide group, a phosphonic acid group, a hydroxyethyl group, a 2-methacryloyloxyethyl group, a 2,2,2-trifluoroethyl group, or a butyl group. Additional functional groups that can be used in the graft copolymer pretreatment composition are detailed below. In some cases, the functional moiety is attached to the backbone via a linker group, such as substituted or unsubstituted alkyl, substituted or unsubstituted alkenyl, or substituted or unsubstituted carbonyl (eg, substituted or unsubstituted carboxyl).
[0045] In some cases, the linear polymer structure can be prepared from diene-containing monomers to form the backbone according to Formula II below: [ka] In formula II, n ranges from 10 to 1000 (e.g., 15 to 750, 20 to 700, 25 to 650, 50 to 600, 100 to 500, or 200 to 400). Also in formula II, R includes a functional moiety that can impart functional pretreatment properties to the metal surface (e.g., the functional moiety can be a corrosion inhibitor, adhesion promoter, lubricant, moisturizer, and / or weld promoter, as described below). Optionally, the functional moiety can include an ethylene oxide group, a phosphonic acid group, a hydroxyethyl group, a 2-methacryloyloxyethyl group, a 2,2,2-trifluoroethyl group, or a butyl group. Additional functional groups that can be used in the graft copolymer pretreatment composition are detailed below. In some cases, the functional moiety is attached to the backbone via a linker group, such as a substituted or unsubstituted alkyl, a substituted or unsubstituted alkenyl, or a substituted or unsubstituted carbonyl (e.g., a substituted or unsubstituted carboxyl). In some examples, one or more double bonds present in formula II may be in the E configuration. In some examples, one or more double bonds present in formula II may be in the Z configuration.
[0046] In some cases, the linear polymer structure can be prepared from acrylic- or methacrylic-containing monomers to form the backbone according to Formula III below: [ka] In formula III, n ranges from 10 to 1000 (e.g., 15 to 750, 20 to 700, 25 to 650, 50 to 600, 100 to 500, or 200 to 400). Also in formula III, R includes a functional moiety that can impart functional pretreatment properties to the metal surface (e.g., the functional moiety can be a corrosion inhibitor, adhesion promoter, lubricant, moisturizer, and / or weld promoter, as described below). Optionally, the functional moiety can include an ethylene oxide group, a phosphonic acid group, a hydroxyethyl group, a 2-methacryloyloxyethyl group, a 2,2,2-trifluoroethyl group, or a butyl group. Additional functional groups that can be used in the graft copolymer pretreatment composition are detailed below. In some cases, the functional moiety is attached to the backbone via a linker group, such as a substituted or unsubstituted alkyl, a substituted or unsubstituted alkenyl, or a substituted or unsubstituted carbonyl (e.g., a substituted or unsubstituted carboxyl). Additionally, in Formula III, when the polymer is prepared from an acrylic-containing monomer, X is hydrogen, and in Formula III, when the polymer is prepared from a methacrylic-containing monomer, X is methyl.
[0047] Surface Bonds or Interfaces As further described below, the surface-bonding or bonding moiety can bond or bond the linear polymer structure described herein to the metal surface by covalent bonds, ionic bonds, hydrogen bonds, dipole interactions, or any combination thereof. In some aspects, the surface-bonding or bonding moiety is a reactive group that can react with the metal surface to form a covalent bond. Exemplary reactive groups include, for example, phosphorus-containing moieties (e.g., phosphoric acid, phosphonic acid), silicon-containing moieties (e.g., siloxanes and silanes), sulfur-containing moieties (e.g., sulfuric acid, sulfonic acid), carboxylic acids (e.g., acrylic acid, methacrylic acid), or metal hydrides. In some cases, the reactive group can be optionally replaced with a substituent (e.g., additional hydroxyl groups) that can provide additional covalent bonds. For example, the hydroxyl functional group of the phosphorus-containing moiety or silicon-containing moiety can react directly with, for example, the metal atom of the metal product at the surface of the metal product to form a metal-oxygen-phosphorus bond or a metal-oxygen-silicon bond in a condensation reaction. Optionally, the reactive groups of the graft copolymer pretreatment composition can react with the oxide surface layer of the metal article.
[0048] Functional part In certain embodiments, the graft copolymer pretreatment compositions described herein further comprise at least one functional moiety that imparts functionalization to the metal surface. For example, the at least one functional moiety can be an adhesion promoter, an adhesive, a lubricant, a moisturizer, a corrosion inhibitor, a welding promoter, or any combination thereof. In some examples, the graft copolymer pretreatment compositions described herein comprise an adhesion promoting functional moiety. In certain examples, the adhesion promoting functional moiety can be a hydroxyl group, an amine group, a carboxylic acid group, an amide group, a thiol group, an epoxide group, a vinyl group, a diol group, or a combination thereof.
[0049] In some examples, the graft copolymer pretreatment composition described herein includes a lubricating moiety. For example, the lubricating moiety can be polyethylene glycol, polytetrahydrofuran, polyisobutene, polybutadiene, polyisoprene, polysiloxane, or any combination thereof. The incorporation of a lubricating moiety can disrupt the surface tension between stacked metal products, thereby improving the destacking ability. Furthermore, the incorporation of a lubricating moiety can improve formability, for example, by reducing and / or stabilizing the frictional forces between the forming die and the sheet metal surface, reducing the occurrence of ears, reducing the rate of wrinkles and curls, increasing the processing speed, reducing galling, extending tool life, and improving the surface quality of the formed metal parts.
[0050] In some examples, the graft copolymer pretreatment compositions described herein may include a moisturizing moiety. For example, the moisturizing moiety may be polypropylene glycol, hexylene glycol, butylene glycol, lactic acid, sodium hexametaphosphate, glycerol, sorbitol, xylitol, maltitol, urea, or any combination thereof. The incorporation of a moisturizing moiety may disrupt the surface tension between the metal surface and certain aqueous solutions (e.g., additional pretreatment compositions, coatings, cleaning solutions, etc., or any combination thereof). Furthermore, the incorporation of a moisturizing moiety may provide a metal surface suitable for downstream coating processes, resulting in more efficient coating processes, more uniform coating coverage, and less coating waste.
[0051] In some examples, the graft copolymer pretreatment compositions described herein include a corrosion-inhibiting functional moiety. In some cases, the corrosion-inhibiting functional moiety is a galvanic corrosion inhibitor (e.g., an inorganic chemical corrosion inhibitor, an organic corrosion inhibitor, or any combination thereof), or a barrier-type corrosion inhibitor (e.g., an inorganic barrier-type corrosion inhibitor, an organic barrier-type corrosion inhibitor, or any combination thereof). In certain aspects, the graft copolymer pretreatment compositions described herein may include one or more inorganic chemical corrosion inhibitors. Inorganic chemical corrosion inhibitors for use in the pretreatment compositions include any inorganic species that can chemically inhibit or prevent corrosion of aluminum alloys, such as by reacting to form a different chemical (e.g., oxide) on the surface of the alloy and / or embedding in the coating to further protect the surface metal. In certain cases, the graft copolymer pretreatment compositions may optionally include an organic corrosion inhibitor. Non-limiting examples of suitable organic corrosion inhibitors include mercaptobenzothiazole (MBT), benzotriazole (BTA), salicylaldoxime, dithiooxamide, quinaldic acid, thioacetamide, 8-hydroxyquinoline (HXQ), and mixtures thereof.
[0052] In some examples, the inorganic chemical corrosion inhibitors described herein include one or more transition metals or salts thereof and / or one or more rare earth metals or salts thereof. Transition metals suitable for use as inorganic chemical corrosion inhibitors include, for example, titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), zirconium (Zr), niobium (Nb), molybdenum (Mo), ruthenium (Ru), rhodium (Rh), palladium (Pd), silver (Ag), cadmium (Cd), hafnium (Hf), tantalum (Ta), tungsten (W), rhenium (Re), osmium (Os), iridium (Ir), platinum (Pt), or gold (Au). Rare earth metals suitable for use as inorganic chemical corrosion inhibitors include, for example, cerium (Ce), scandium (Sc), yttrium (Y), lanthanum (La), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), and lutetium (Lu).
[0053] Optionally, the inorganic chemical corrosion inhibitor is a transition metal salt or a rare earth metal salt. Optionally, the transition metal salt or the rare earth metal salt comprises a transition metal salt or a rare earth metal in an oxidation state of +1, +2, +3, +4, +5, or +6. For example, the transition metal salt or the rare earth metal salt can be a salt comprising molybdenum II ions, molybdenum III ions, molybdenum IV ions, molybdenum V ions, molybdenum VI ions, zirconium II ions, zirconium III ions, zirconium IV ions, titanium II ions, titanium III ions, titanium IV ions, cerium II ions, cerium III ions, or cerium IV ions. In a particular example, the above metal ions can be incorporated between at least two layers of the graft copolymer pretreatment composition described herein to enhance corrosion resistance. For example, a metal product can be coated with the graft copolymer pretreatment composition to form a layer. Metal ions can be deposited on the graft copolymer pretreatment composition layer. Optionally, an additional layer of the graft copolymer pretreatment composition can be applied to the resulting product.
[0054] In some cases, the rare earth metal salt can be an anhydrous salt. In some cases, the rare earth metal salt can be a hydrated salt, such as a monohydrate, dihydrate, trihydrate, tetrahydrate, pentahydrate, hexahydrate, heptahydrate, octahydrate, nonahydrate, and / or decahydrate salt. In some examples, the rare earth metal salt is a rare earth metal nitrate. Examples of suitable inorganic chemical corrosion inhibitors include cerium(III) nitrate hexahydrate (Ce(NO3)3·6H2O), yttrium nitrate hexahydrate (Y(NO3)3·6H2O), ytterbium nitrate hexahydrate (Yb(NO3)3·6H2O), and lanthanum nitrate hexahydrate (La(NO3)3·6H2O).
[0055] In certain aspects, multiple layers of the graft copolymer pretreatment composition described herein can impart corrosion resistance to metal surfaces. For example, a corrosion-preventing coating can include at least a first layer having a graft copolymer pretreatment composition that includes an anionic functional group (e.g., phosphonic acid) and at least a second layer that includes a multivalent cation (e.g., any transition metal ion). Optionally, the multiple layers can include a third layer having a graft copolymer pretreatment composition that includes a phosphonic acid functional group. As used herein, multiple layers can refer to a series of thin films deposited on a metal surface. For example, multiple layers of a graft copolymer pretreatment composition can include a first layer deposited on a metal surface that completely covers the metal surface. A subsequent layer can then be deposited on the first layer that completely covers the first layer, and so on. In certain cases, multiple layers can refer to the sequential deposition of multiple layers of a graft copolymer pretreatment composition that form a single fused layer. The composition and morphology of a single fused layer may depend on the surface moisturization of each of the graft copolymer pretreatment compositions, the miscibility of any solvent used to carry the graft copolymer pretreatment composition, or the designed location of each of the multiple layers of the graft copolymer pretreatment composition. Thus, a metal surface can be pretreated with multiple layers of the graft copolymer pretreatment composition in a layer-by-layer, mixed, or any desired thin film form.
[0056] In some examples, the graft copolymer pretreatment compositions described herein include a welding promotion moiety. The incorporation of the welding promotion moiety can disrupt the surface tension between metal products that contact during a welding process (e.g., resistance spot welding, resistance seam welding, friction stir welding, gas metal arc welding (e.g., metal inert gas welding or tungsten inert gas welding), plasma arc welding, laser welding, refill friction stir spot welding, any suitable welding process, or any combination thereof). In some embodiments, the welding promotion moiety can include titanium (Ti), zirconium (Zr), or a combination thereof.
[0057] In some examples, the graft copolymer pretreatment composition described herein includes a crosslinkable functional moiety. For example, a metal article can be coated with the graft copolymer pretreatment composition to form a layer. A crosslinking agent can then be applied to form covalent or non-covalent bonds with the crosslinkable functional moiety of the graft copolymer pretreatment composition layer to link two or more individual polymer chains. Alternatively, a crosslinking precursor can be pre-incorporated into the graft copolymer pretreatment composition and activated by an external stimulus (e.g., heat, light, pH, mechanical activation, etc.).
[0058] The crosslinking agent can be a small functional organic molecule (e.g., a bifunctional organic molecule) or a multifunctional organic molecule that reacts with the corresponding crosslinkable functional moieties in the graft copolymer pretreatment composition layer. Examples include, but are not limited to, 1,4 phenylenediacryloyl chloride or polyglycidyl ether cyclosiloxanes (e.g., CS-697), which react with hydroxy or amino functional groups in the graft copolymer composition to form interchain bonds, alkyldithiols in the presence of disulfide moieties, and poly(ethylene glycol) bisazides in the presence of alkynes.
[0059] Optionally, divalent or polyvalent metal ions can be applied to the graft copolymer pretreatment composition layer to crosslink suitable crosslinkable moieties in the composition. Moieties that form crosslinks in the presence of divalent or polyvalent metal ions include, but are not limited to, carboxylic acid groups, phosphonic acid groups, and / or sulfonic acid groups. Inorganic chemical crosslinkers described herein include, but are not limited to, polyvalent metal cations, such as alkaline earth metals or salts thereof, and / or one or more transition metals or salts thereof, and / or one or more rare earth metals or salts thereof. Metal ions can be applied from a solution, including an aqueous solution, resulting in instantaneous crosslinking. Metals suitable for use as inorganic chemical crosslinkers include, for example, beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), zirconium (Zr), niobium (Nb), molybdenum (Mo), ruthenium (Ru), rhodium (Rh), palladium (Pd), silver (Ag), cadmium (Cd), hafnium (Hf), tantalum (Ta), tungsten (W), rhenium (Re), osmium (Os), iridium (Ir), platinum (Pt), or gold (Au). Suitable rare earth metals for use as inorganic chemical corrosion inhibitors include, for example, cerium (Ce), scandium (Sc), yttrium (Y), lanthanum (La), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), and lutetium (Lu). Certain metal ions can simultaneously contribute to multiple functions, such as corrosion inhibition and crosslinking. In certain embodiments, the crosslinking agent is a zirconium salt or complex, such as zirconium bis(acetylacetonate).
[0060] Exemplary Graft Copolymer Pretreatment Compositions In some examples, the graft copolymer pretreatment compositions described herein can provide a multi-functional surface coating to a metal surface along with a bonding or interfacing portion. In some cases, the graft copolymer pretreatment composition can include any combination of bonding or interfacing portions, corrosion prevention functional portions, adhesion promoting functional portions, lubricating functional portions, moisturizing functional portions, and / or weld promoting functional portions. For example, the graft copolymer pretreatment can include a bonding or interfacing portion and a lubricating functional portion. In some cases, the graft copolymer pretreatment can include a bonding or interfacing portion and a corrosion prevention portion. In some cases, the graft copolymer pretreatment can include a bonding or interfacing portion and an adhesion promoting portion. In some other cases, the graft copolymer pretreatment can include a bonding or interfacing portion, a lubricating functional portion, and an adhesion promoting portion. In certain examples, the graft copolymer pretreatment can include a bonding or interfacing portion, a lubricating functional portion, and a moisturizing portion. Additionally, the graft copolymer pretreatment can include a bonding or interfacing portion and a moisturizing portion. Additionally, the graft copolymer pretreatment can include a bonding or interfacing portion and a weld promoting portion. In some non-limiting examples, the pretreatment of the graft copolymer may include a bonding or interfacing moiety, a corrosion inhibition moiety, and an adhesion promoting moiety. In certain aspects, the pretreatment of the graft copolymer may include a bonding or interfacing moiety, a corrosion inhibition moiety, an adhesion promoting moiety, and a lubricating functional moiety. In some examples, the pretreatment of the graft copolymer may include a bonding or interfacing moiety, a corrosion inhibition moiety, an adhesion promoting moiety, and a weld promoting moiety. In some aspects, the pretreatment of the graft copolymer may include a bonding or interfacing moiety, a corrosion inhibition moiety, and a lubricating functional moiety. These are some non-limiting examples, as the pretreatment of the graft copolymer may include any combination of a bonding or interfacing moiety and any suitable functional moiety.
[0061] An exemplary graft copolymer pretreatment composition described herein that includes a surface-attaching moiety and a functional moiety is shown below in Formula IV: [ka] In formula IV, X 1, X 2 , X 3 , and X 4 are each independently selected from hydrogen and methyl. Also in formula IV, each of m, n, o, and p is independently optionally present in the range of 1 to 1000 (e.g., 1 to 100, 1 to 50, or 1 to 30). In some examples, one or more of m, n, o, and p are present (e.g., two of m, n, o, and p are present; three of m, n, o, and p are present; or each of m, n, o, and p are present). Further in formula IV, R 1 , R 2 , R 3 , and R 4 each independently, if present, is -O- or -NR 6 -, wherein R 6 is substituted or unsubstituted alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted alkynyl, substituted or unsubstituted aryl, substituted or unsubstituted heteroaryl, substituted or unsubstituted cycloalkyl, or substituted or unsubstituted heterocycloalkyl. 5 is a spacer group, e.g. (CH2) q wherein q is in the range of 1 to 30 (e.g., q=1 to 30, q=1 to 25, q=1 to 20, q=1 to 15, q=1 to 10, q=1 to 5, q=5-30 q=5 to 25, q=5 to 20, q=5 to 15, q=5-10 q=10 to 30, q=10 to 25, q=10 to 20, q=10 to 15, q=15 to 30, q=15 to 25, q=15 to 20, q=20 to 30, q=20 to 25, or q=25 to 30).
[0062] Further in formula IV, A is a surface-bonding or conjugating moiety as described herein. Optionally, A is selected from the group consisting of phosphonic acid (PO3H2), carboxylic acid (COOH), trialkoxysilyl group (-Si(OR)3, where R is an alkyl, alkenyl, alkynyl, heteroalkyl, heteroalkenyl, heteroalkynyl cycloalkyl, cycloalkenyl, cycloalkynyl, heterocycloalkyl, heterocycloalkenyl, or heterocycloalkynyl group), and / or various catechol derivatives as shown in formulas V and VI below: [ka] In Formula V and Formula VI, R 7 is selected from hydrogen, a hydroxyl group, an electron-withdrawing group (eg, a nitro group, a carboxy group, or a halide (eg, fluoride, chloride, bromide, or iodide)).
[0063] In some examples, Pol in formula IV is an optionally present functional moiety. In some examples, Pol is a polymer chain such as a poly(ethylene glycol) chain, a poly(tetrahydrofuran) chain, a poly(isoprene) chain, a hydrogenated poly(isoprene) chain, a poly(isoprene) chain, a (butadiene) chain, a hydrogenated poly(butadiene) chain, or a polyisobutene chain that can function as a lubricant.
[0064] In some cases, FG in formula IV is an optional functional moiety, which may be an adhesive compound or any other functional moiety described herein. Optionally, FB may be hydroxyl, amide, thiol, epoxide, vinyl, diol, phosphonic acid, carboxylic acid, sulfonic acid, polyvalent cation including any transition metal ion, or any rare earth metal ion. In some non-limiting examples, when FG is phosphonic acid, any one of molybdenum ion, zirconium ion, or titanium ion may be incorporated into the graft copolymer pretreatment composition. In some cases, FG may be a halide, ethylene oxide, trialkoxysilyl, hydroxyethyl group, 2-methacryloyloxyethyl group, 2,2,2-trifluoroethyl group, or butyl group.
[0065] Aluminum alloys treated with graft copolymer pretreatment compositions Disclosed herein are metals and alloys, e.g., aluminum alloys, comprising at least one surface treated with the graft copolymer pretreatment composition described herein. The coatings described herein are suitable for providing corrosion protection, improved adhesion, lubrication, improved moisture retention, and / or improved welding performance to any metal or alloy, e.g., aluminum alloys. The graft copolymer pretreatment compositions disclosed herein may also be referred to as coatings, films, or layers. Although aluminum alloys are described and exemplified, the compositions and methods described herein may also be used to treat other metals and alloys, including mild steel, galvanized steel, and magnesium alloys, as described above.
[0066] The disclosed coated metals and / or alloys have a surface coating layer that includes a polymeric backbone (e.g., a linear polymer polymerized from acrylic or methacrylic monomers), at least one phosphonate linking moiety attached to the polymeric backbone and configured to bond a graft copolymer pretreatment composition to the metal and / or alloy surface, and at least one functional moiety attached to the polymeric backbone and configured to impart surface functionalization to the metal and / or alloy surface. As discussed above, surface functionalization includes corrosion resistance, improved adhesion, lubricity, improved moisture retention, and / or improved welding performance.
[0067] Optionally, the method includes degreasing the aluminum alloy surface and / or etching the aluminum alloy surface prior to applying the coating. The method may further include cleaning the aluminum alloy, rinsing the aluminum alloy, and drying the aluminum alloy prior to applying the pretreatment solution.
[0068] In some examples, at least one surface of a metal and / or alloy (e.g., an aluminum alloy substrate, such as an aluminum alloy coil) can be coated by applying a graft copolymer pretreatment composition described herein to the alloy to form an initial coating layer. The pretreatment composition can be applied to at least one surface of the aluminum alloy by any suitable method. In some cases, the graft copolymer pretreatment composition is coated from a solution containing the graft copolymer pretreatment composition (e.g., an aqueous graft copolymer pretreatment solution, an organic solvent graft copolymer pretreatment solution, or a combination thereof). For example, the coating described herein can be applied by roll coating, spray coating, dip coating, electrodeposition, glaze coating, or drop coating a suitable graft copolymer pretreatment solution. These methods are generally known in the art.
[0069] Optionally, after application of the graft copolymer pretreatment solution, the graft copolymer pretreatment solution can be cured to form an aluminum alloy comprising a coating layer of the graft copolymer pretreatment composition. For example, curing the graft copolymer pretreatment solution can be used to cure the metal or alloy and / or the graft copolymer pretreatment solution to a temperature above the glass transition temperature (T g ) to remove residual solvent without adversely affecting the graft copolymer pretreatment composition in solution. After curing, the graft copolymer pretreatment composition becomes a coating layer having the desired graft copolymer pretreatment composition (e.g., any one, any combination, or all of a corrosion inhibitor, an adhesion promoter, a lubricant, a humectant, a welding promoter, a hydrophobic functionality (e.g., a self-cleaning and / or water repellent surface), an oleophobic functionality (e.g., an antifouling surface), a hydrophilic functionality (e.g., a biocompatible surface), an optical functionality (e.g., a dye, a pigment, an optical waveguide, a photoluminescent surface, or a negative refractive index surface), or any combination thereof).
[0070] Optionally, after applying the graft copolymer pretreatment solution, the polymer layer can be crosslinked by applying a crosslinking agent or a solution thereof by incubation, dipping, rolling, spraying, or any suitable application technique. Crosslinking improves the structural stability and robustness of the graft copolymer pretreatment composition layer. Upon contact with a good solvent, typically water, the crosslinked polymer layer swells and forms a polymer gel layer. The polymer gel exhibits viscoelastic properties that can improve lubricity.
[0071] Optionally, the coated aluminum alloy may be part of a bonded structure that includes the coated aluminum alloy and a second metal or alloy of different composition, for example, the coated aluminum alloy may be a 1xxx series alloy, a 2xxx series alloy, a 3xxx series alloy, a 4xxx series alloy, a 5xxx series alloy, a 6xxx series alloy, a 7xxx series alloy, or an 8xxx series alloy made from a cast aluminum alloy product bonded to another alloy or metal.
[0072] Optionally, the aluminum alloy may be a 1xxx series aluminum alloy according to one of the following aluminum alloy designations: AA1100, AA1100A, AA1200, AA1200A, AA1300, AA1110, AA1120, AA1230, AA1230A, AA1235, AA1435, AA1145, AA1345, AA1445, AA1150, AA1350, AA1350A, AA1450, AA1370, AA1275, AA1185, AA1285, AA1385, AA1188, AA1190, AA1290, AA1193, AA1198, or AA1199.
[0073] Optionally, the aluminum alloy may be a 2xxx series aluminum alloy according to one of the following aluminum alloy designations: AA2001, A2002, AA2004, AA2005, AA2006, AA2007, AA2007A, AA2007B, AA2008, AA2009, AA2010, AA2011, AA2011A, AA2111, AA2111A, AA2111B, AA2 012, AA2013, AA2014, AA2014A, AA2214, AA2015, AA2016, AA2017, AA2017A, AA2117, AA2018, AA2218, AA2618, AA2618A, AA2219, AA2319, AA2419, AA2519, AA2021, AA2022, AA2023, AA2024, AA2024A, AA2124, AA2224, AA22 24A, AA2324, AA2424, AA2524, AA2624, AA2724, AA2824, AA2025, AA2026, AA2027, AA2028, AA2028A, AA2028B, AA2028C, AA2029, AA2030, AA2031, AA2032, AA2034, AA2036, AA2037, AA2038, AA2039, AA2139, AA2040, AA204 1, AA2044, AA2045, AA2050, AA2055, AA2056, AA2060, AA2065, AA2070, AA2076, AA2090, AA2091, AA2094, AA2095, AA2195, AA2295, AA2196, AA2296, AA2097, AA2197, AA2297, AA2397, AA2098, AA2198, AA2099, or AA2199.
[0074] Optionally, the aluminum alloy may be a 3xxx series aluminum alloy according to one of the following aluminum alloy designations: AA3002, AA3102, AA3003, AA3103, AA3103A, AA3103B, AA3203, AA3403, AA3004, AA3004A, AA3104, AA3204, AA3304, AA3005, AA3005A, AA3105, AA3105 A, AA3105B, AA3007, AA3107, AA3207, AA3207A, AA3307, AA3009, AA3010, AA3110, AA3011, AA3012, AA3012A, AA 3013, AA3014, AA3015, AA3016, AA3017, AA3019, AA3020, AA3021, AA3025, AA3026, AA3030, AA3130, or AA3065.
[0075] Optionally, the aluminum alloy may be a 4xxx series aluminum alloy according to one of the following aluminum alloy designations: AA4004, AA4104, AA4006, AA4007, AA4008, AA4009, AA4010, AA4013, AA4014, AA4015, AA4015A, AA4115, AA4016, AA4017, AA4018, AA4019, AA4020, AA4021, AA4026, AA4032, AA4043, AA4043A, AA4143, AA4343, AA4643, AA4943, AA4044, AA4045, AA4145, AA4145A, AA4046, AA4047, AA4047A, or AA4147.
[0076] Optionally, the aluminum alloy may be a 5xxx series aluminum alloy according to one of the following aluminum alloy designations: AA5005, AA5005A, AA5205, AA5305, AA5505, AA5605, AA5006, AA5106, AA5010, AA5110, AA5110A, AA5210, AA5310, AA5016, AA5017, AA5018, AA5018A, AA5019, AA5019A , AA5119, AA5119A, AA5021, AA5022, AA5023, AA5024, AA5026, AA5027, AA5028, AA5040, AA5140, AA5041, AA5042, AA504 3, AA5049, AA5149, AA5249, AA5349, AA5449, AA5449A, AA5050, AA5050A, AA5050C, AA5150, AA5051, AA5051A, AA5151, AA 5251, AA5251A, AA5351, AA5451, AA5052, AA5252, AA5352, AA5154, AA5154A, AA5154B, AA5154C, AA5254, AA5354, AA545 4, AA5554, AA5654, AA5654A, AA5754, AA5854, AA5954, AA5056, AA5356, AA5356A, AA5456, AA5456A, AA5456B, AA5556, AA 5556A, AA5556B, AA5556C, AA5257, AA5457, AA5557, AA5657, AA5058, AA5059, AA5070, AA5180, AA5180A, AA5082, AA5182, AA5083, AA5183, AA5183A, AA5283, AA5283A, AA5283B, AA5383, AA5483, AA5086, AA5186, AA5087, AA5187, or AA5088.
[0077] Optionally, the aluminum alloy may be a 6xxx series aluminum alloy with one of the following aluminum alloy designations: AA6101, AA6101A, AA6101B, AA6201, AA6201A, AA6401, AA6501, AA6002, AA6003, AA6103, AA6005, AA6005A, AA6005B, AA6005C, AA6105, AA6205, AA6305, AA6006, AA 6106, AA6206, AA6306, AA6008, AA6009, AA6010, AA6110, AA6110A, AA6011, AA6111, AA6012, AA6012A, AA6013, AA6113 , AA6014, AA6015, AA6016, AA6016A, AA6116, AA6018, AA6019, AA6020, AA6021, AA6022, AA6023, AA6024, AA6025, AA602 6, AA6027, AA6028, AA6031, AA6032, AA6033, AA6040, AA6041, AA6042, AA6043, AA6151, AA6351, AA6351A, AA6451, AA6 951, AA6053, AA6055, AA6056, AA6156, AA6060, AA6160, AA6260, AA6360, AA6460, AA6460B, AA6560, AA6660, AA6061, AA 6061A, AA6261, AA6361, AA6162, AA6262, AA6262A, AA6063, AA6063A, AA6463, AA6463A, AA6763, A6963, AA6064, AA6064A, AA6065, AA6066, AA6068, AA6069, AA6070, AA6081, AA6181, AA6181A, AA6082, AA6082A, AA6182, AA6091, or AA6092.
[0078] Optionally, the aluminum alloy may be a 7xxx series aluminum alloy according to one of the following aluminum alloy designations: AA7011, AA7019, AA7020, AA7021, AA7039, AA7072, AA7075, AA7085, AA7108, AA7108A, AA7015, AA7017, AA7018, AA7019A, AA7024, AA7025, AA7028, AA7030, AA7031, AA7033, AA7035, AA7035A, AA7046, AA7046A, AA7003, AA7004, AA7005, AA7009, AA7010, AA7011, AA7012, AA7014, AA7016, AA7116, AA7122, AA7023, AA 7026, AA7029, AA7129, AA7229, AA7032, AA7033, AA7034, AA7036, AA7136, AA7037, AA7040, AA71 40, AA7041, AA7049, AA7049A, AA7149, AA7249, AA7349, AA7449, AA7050, AA7050A, AA7150, AA725 0, AA7055, AA7155, AA7255, AA7056, AA7060, AA7064, AA7065, AA7068, AA7168, AA7175, AA7475, AA7076, AA7178, AA7278, AA7278A, AA7081, AA7181, AA7185, AA7090, AA7093, AA7095, or AA7099.
[0079] Optionally, the aluminum alloy may be an 8xxx series aluminum alloy according to one of the following aluminum alloy designations: AA8005, AA8006, AA8007, AA8008, AA8010, AA8011, AA8011A, AA8111, AA8211, AA8112, AA8014, AA8015, AA8016, AA8017, AA8018, AA8019, AA8021, AA8021A, AA8021B, AA8022, AA8023, AA8024, AA8025, AA8026, AA8030, AA8130, AA8040, AA8050, AA8150, AA8076, AA8076A, AA8176, AA8077, AA8177, AA8079, AA8090, AA8091, or AA8093.
[0080] Optionally, the coated aluminum alloy can be provided in any metallurgical state, such as any suitable temper or temper. For example, the aluminum alloy can be provided in the F, O, or W temper, as described above. In some cases, heat-treatable aluminum alloys (e.g., 2xxx series aluminum alloys, 6xxx series aluminum alloys, 7xxx series aluminum alloys, and certain 8xxx aluminum alloys) can be subjected to natural aging and / or artificial aging. As described herein, natural aging includes storing the age-hardenable aluminum alloy at a temperature of about room temperature for a period of time to provide an age-hardenable aluminum alloy in a T1, T2, T3, or T4 temper. Optionally, the age-hardenable aluminum alloy can be subjected to artificial aging, which includes heating the aluminum alloy to an elevated temperature below the liquidus temperature of the aluminum alloy to provide an age-hardenable aluminum alloy in a T5, T6x, T7, T8x, or T9 temper. In other examples, strain hardening aluminum alloys (e.g., 1xxx series aluminum alloys, 3xxx series aluminum alloys, 4xxx series aluminum alloys, 5xxx series aluminum alloys, and certain 8xxx series aluminum alloys) may be subjected to strain hardening treatment to provide strain hardening aluminum alloys in the above-mentioned Hxx tempers. As described herein, strain hardening treatment includes cold working and optionally annealing the strain hardening aluminum alloy to provide strain hardening aluminum alloys in H tempers, such as Hx1, Hx2, Hx3, Hx4, Hx5, Hx6, and Hx7, Hx8, or Hx9 tempers.
[0081] The coated aluminum alloy can be processed into an aluminum alloy product, such as an aluminum alloy plate, sheet, or shade. In some examples, the alloy can be processed into an aluminum alloy sheet including a graft copolymer coating described herein having any desired functionality. In some examples, the alloy can be fabricated into a shaped product formed from any aluminum alloy sheet described herein and including any coating layer formed from a graft copolymer pretreatment composition described herein. In some examples, the aluminum alloy is a shaped product formed from any aluminum alloy sheet described herein and including any graft copolymer coating described herein, and the shaped product is joined to another product formed from a different alloy or different metal (e.g., a second alloy or second metal). In some non-limiting examples, the aluminum alloy and the second metal and / or alloy are joined to form a joint of any suitable configuration, including lap, edge, butt, T-butt, hem, T-edge, etc.
[0082] The disclosed graft copolymer coatings and methods tailor the surface properties of aluminum and aluminum alloys. Aluminum alloys that may find utility from the protective coating layers disclosed herein include those used in the automotive industry (e.g., automotive joints), manufacturing applications, electronics applications, industrial applications, and the like. Optionally, the alloy is part of a joint structure, such as, for example, the chassis of an automobile or other motor vehicle. The chassis may be in a white stage body or painted.
[0083] Polymer synthesis The polymers for the pretreatment compositions described herein can be prepared by synthesizing a polymer having surface-attached or tethered moieties and functional moieties by polymerizing or copolymerizing suitable monomers by chain polymerization methods such as radical polymerization, cationic polymerization, anionic polymerization, catalytic polymerization, or functional group transfer polymerization. Optionally, the polymer backbone is a homopolymer backbone provided by polymerizing a single type of repeat unit (e.g., monomer). Optionally, the polymer backbone can be a copolymer backbone provided by polymerizing a variety of different monomers by chain polymerization methods such as radical polymerization, cationic polymerization, anionic polymerization, catalytic polymerization, or functional group transfer polymerization. Each repeat unit can include a surface-attached or tethered moiety, a functional moiety, both a surface-attached or tethered moiety and a functional moiety, or the repeat unit can lack a pendant functional moiety (e.g., a backbone spacer).
[0084] In some non-limiting cases, polymers for the pretreatment compositions described herein can be prepared by radical polymerization or copolymerization of methacrylic or acrylic monomers, such as methyl methacrylate, methacryloyloxy(methyl)phosphonic acid (MMPA), hydroxylethyl methacrylate (HEMA), or poly(ethylene glycol) methyl ether methacrylate (PEGMEMA), to synthesize a polymer backbone having surface-binding moieties and optional functional moieties. The number average molecular weight (M n ) can be, for example, in the range of 300 to 5000 (e.g., 300, 400, 700, 1000, 2000, or 5000).
[0085] In certain embodiments, the polymerization is carried out by dissolving a monomer (e.g., M) in a solvent (e.g., water, methanol, ethanol, isopropanol, n-butanol, dimethylformamide, dimethylsulfoxide, acetonitrile, acetone, tetrahydrofuran, methyl ethyl ketone, or any combination thereof). n= 2000 (PEGMEMA-2000), an initiator (e.g., ammonium persulfate (APS)), and a base (e.g., N,N,N',N'-tetramethylenediamine (TEMED)) in a predetermined stoichiometric ratio. Furthermore, copolymer polymerization can be carried out in a solvent as described above using at least two monomers (e.g., PEGMEMA-2000 and (methacryloyloxy)methylphosphonic acid (MMPA)), an initiator (e.g., APS), and a base (e.g., TEMED) in a predetermined stoichiometric ratio. An exemplary synthetic method for preparing a polymer for the pretreatment composition described herein is detailed in Example 1 below.
[0086] How to use The disclosed aluminum alloy products provided in the tempers described herein may be incorporated into existing processes and lines for the manufacture of aluminum alloy products, such as hot formed aluminum products (e.g., hot formed automotive structural components), thereby improving the processes and resulting products in a streamlined and economical manner. Systems and methods for carrying out the forming processes and producing the products described herein are included within the scope of this disclosure.
[0087] The described aluminum alloy products and processes may be advantageously employed in the transportation industry, including, but not limited to, automobile manufacturing, truck manufacturing, ship and boat manufacturing, train manufacturing, airplane and spacecraft manufacturing. Some non-limiting examples of automobile parts include floor panels, rear walls, rockers, motor hoods, fenders, roofs, door panels, B-pillars, body sides, rockers, or impact members. The term "automobile" and related terms used herein are not limited to automobiles, but include various vehicle classifications, such as automobiles, cars, buses, motorcycles, marine vessels, off-highway vehicles, light trucks, trucks, or lorries. However, the aluminum alloy products are not limited to automobile parts, and other types of aluminum products manufactured according to the processes described herein are envisioned. For example, the described processes may be advantageously employed in the manufacture of various parts of mechanical and other devices or mechanisms, including weapons, tools, electronic device bodies, and other parts and devices.
[0088] The aluminum alloy products and processes described herein can also be used in electronics applications, such as to make external and internal containers. For example, the alloys and methods described herein can be used to make housings for electronic devices, including mobile phones and tablet computers. In some examples, the alloys can be used to make housings for the external casings of mobile phones (e.g., smartphones) and the bottom chassis of tablets.
[0089] Examples of Suitable Compositions, Products, and Methods Example 1 is a graft copolymer pretreatment composition comprising: a polymer backbone; at least one surface binding or bonding moiety attached to the polymer backbone and configured to bond or bond the polymer backbone to a first surface of a metal article; at least one functional moiety attached to the polymer backbone and configured to provide at least a first surface functionalization to the first surface of the metal article; and at least one second functional moiety attached to the polymer backbone and configured to provide at least a second surface functionalization to the first surface of the metal article, where the at least one functional moiety and the at least one second functional moiety provide a multi-functional surface coating.
[0090] Example 2 is any of the above or below described exemplary graft copolymer pretreatment compositions in which the polymer backbone comprises an acrylic class of linear polymer structures, a methacrylic class of linear polymer structures, a vinyl class of linear polymer structures, a diene class of linear polymer structures, a vinylidene class of linear polymer structures, or any combination thereof.
[0091] Example 3 is any of the above or below described exemplary graft copolymer pretreatment compositions, wherein the polymer backbone is poly(methyl methacrylate), poly(ethyl methacrylate), poly(ethyl acrylate), polyacrylonitrile, polyethylene, polypropylene, polystyrene, poly(vinyl chloride), poly(vinyl acetate), poly(vinyl alcohol), polybutadiene, polyisoprene, polychloroprene, or any combination thereof.
[0092] Example 4 is any of the above or below exemplary graft copolymer pretreatment compositions in which at least one surface-bonding or adhering moiety comprises a phosphonate group, a carboxyl group, a catechol group, or a trialkoxysilyl group.
[0093] Example 5 is any of the above or below exemplary graft copolymer pretreatment compositions in which the phosphonate groups comprise poly(vinyl phosphonate).
[0094] Example 6 is any of the exemplary graft copolymer pretreatment compositions described above or below, where at least one functional moiety comprises an adhesion promoter.
[0095] Example 7 is any of the above or below described exemplary graft copolymer pretreatment compositions in which the adhesion promoter comprises a hydroxyl group, an amide group, a thiol group, an epoxide group, a vinyl group, a diol group, an adhesive composition, a covalent bonding group, or an ionic bonding group.
[0096] Example 8 is any of the exemplary graft copolymer pretreatment compositions described above or below, where at least one functional moiety includes a polymeric side chain that provides a lubricating function.
[0097] Example 9 is any of the exemplary graft copolymer pretreatment compositions described above or below, where the polymer side chains providing the lubricating function include polyethylene glycol, polytetrahydrofuran, polyisobutene, polysilicone, or any combination thereof.
[0098] Example 10 is any of the exemplary graft copolymer pretreatment compositions described above or below in which at least one functional moiety comprises a humectant.
[0099] Example 11 is any of the above or below described exemplary graft copolymer pretreatment compositions, wherein the moisturizer comprises polypropylene glycol, hexylene glycol, butylene glycol, lactic acid, sodium hexametaphosphate, glycerol, sorbitol, xylitol, maltitol, urea, or any combination thereof.
[0100] Example 12 is any of the exemplary graft copolymer pretreatment compositions described above or below, where at least one functional moiety comprises a weld promoter.
[0101] Example 13 is any of the exemplary graft copolymer pretreatment compositions described above or below, where at least one functional moiety comprises a corrosion inhibitor.
[0102] Example 14 is any of the above or below described exemplary graft copolymer pretreatment compositions, wherein the corrosion inhibitor comprises an inorganic corrosion inhibitor, an inorganic barrier type corrosion inhibitor, an organic corrosion inhibitor, an organic barrier type corrosion inhibitor, or any combination thereof.
[0103] Example 15 is any of the above or below described exemplary graft copolymer pretreatment compositions, where the corrosion inhibitor comprises an inorganic corrosion inhibitor, the inorganic corrosion inhibitor comprises a transition metal, a transition metal salt, a rare earth metal, or a rare earth metal salt.
[0104] Example 16 is any of the above or below described exemplary graft copolymer pretreatment compositions, wherein the inorganic corrosion inhibitor comprises a transition metal, the transition metal comprising titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), zirconium (Zr), niobium (Nb), molybdenum (Mo), ruthenium (Ru), rhodium (Rh), palladium (Pd), silver (Ag), cadmium (Cd), hafnium (Hf), tantalum (Ta), tungsten (W), rhenium (Re), osmium (Os), iridium (Ir), platinum (Pt), or gold (Au).
[0105] Example 17 is any of the above or below described exemplary graft copolymer pretreatment compositions, wherein the inorganic corrosion inhibitor comprises a transition metal salt, the transition metal salt comprising a salt of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Cd, Hf, Ta, W, Re, Os, Ir, Pt, or Au.
[0106] Example 18 is any of the above or below described exemplary graft copolymer pretreatment compositions, wherein the inorganic corrosion inhibitor comprises a rare earth metal, the rare earth metal comprising cerium (Ce), scandium (Sc), yttrium (Y), lanthanum (La), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), or lutetium (Lu).
[0107] Example 19 is any of the above or below described exemplary graft copolymer pretreatment compositions, wherein the inorganic corrosion inhibitor comprises a rare earth metal salt, the rare earth metal salt comprising a salt of Ce, Sc, Y, La, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, or Lu.
[0108] Example 20 is any of the above or below described exemplary graft copolymer pretreatment compositions, wherein the corrosion inhibitor comprises an organic corrosion inhibitor, the organic corrosion inhibitor comprising mercaptobenzothiazole, benzotriazole, salicylaldoxime, dithiooxamide, quinaldic acid, thioacetamide, or 8-hydroxyquinoline.
[0109] Example 21 is any of the exemplary graft copolymer pretreatment compositions described above or below, where the at least one second functional moiety comprises an adhesion promoter, a polymeric side chain that provides a lubricating function, a moisturizer, a welding promoter, or a corrosion inhibitor.
[0110] Example 22 is any of the above or below described exemplary graft copolymer pretreatment compositions, where the graft copolymer pretreatment composition is crosslinked with a crosslinking agent.
[0111] Example 23 is any of the above or below exemplary graft copolymer pretreatment compositions in which the crosslinking agent is a zirconium salt or zirconium complex.
[0112] Example 24 is any of the above or below described exemplary graft copolymer pretreatment compositions in which the crosslinking agent is an aqueous solution of a zirconium salt or zirconium complex.
[0113] Example 25 is a method of pretreating at least a portion of a metal surface comprising applying to at least a portion of the metal surface any of the exemplary graft copolymer pretreatment compositions described above or below.
[0114] Example 26 is any preceding or following exemplary method in which applying the graft copolymer pretreatment composition comprises solution coating at least a portion of the metal surface.
[0115] Example 27 is any of the above exemplary methods, where the solution coating comprises roll coating, dip coating, enrobing, spin coating, or spray coating at least a portion of the metal surface.
[0116] The following examples serve to further illustrate the present invention, but do not, however, constitute any limitation thereof: on the contrary, it is to be clearly understood that various embodiments, modifications and equivalents thereof may be resorted to, which may suggest themselves to those skilled in the art after reading the description herein, without departing from the spirit of the invention. EXAMPLES
[0117] Example 1: Polymer synthesis Chemical substances and materials used in polymer synthesis include number average molecular weight (M n ) 2000 poly(ethylene glycol) methyl ether methacrylate (PEGMEMA-2000), M n Poly(ethylene glycol) methyl ether methacrylate (PEGMEMA-950), M n Poly(ethylene glycol) methyl ether methacrylate (PEGMEMA-500), M nPoly(ethylene glycol) methyl ether methacrylate-300 (PEGMEMA-300), 2-hydroxyethyl methacrylate (HEMA), butyl methacrylate (BMA), 2-methacryloyloxyethyl phosphorylcholine (MPC), 2,2,2-trifluoroethyl methacrylate (TFEMA), 4,4'-azobis(4-cyanovaleric acid) (V-501), (methacryloyloxy)methylphosphonic acid (MMPA), ammonium persulfate (APS), N,N,N',N'-tetramethylenediamine (TEMED), and 4-cyano-4-(phenylcarbonothioylthio)pentanoic acid. The products were analyzed by gel permeation chromatography (GPC) and nuclear magnetic resonance (NMR) spectroscopy. [ka]
[0118] Homopolymer 1a: Poly(methacrylate)-graft-poly(ethylene glycol). Polymerization was carried out using PEGMEMA-2000, APS as initiator, and TEMED as base in a stoichiometric ratio of 1.0 / 0.5 / 2.3 equivalents. PEGMEMA-2000 (0.6 g; 50 wt% in water, 0.15 mmol), 17.4 mg of APS (0.076 mmol), and 3 mL of water were added to a Schlenk flask equipped with a magnetic stir bar. The flask was sealed and the solution was subjected to three freeze-pump-thaw cycles. TEMED (52 μL, 0.345 mmol) was then added under positive argon pressure. The flask was resealed and the mixture was stirred at 400 revolutions per minute (rpm) for 2 h at room temperature. Homopolymer 1a was obtained by lyophilization.
[0119] Homopolymer 1b: Poly(methacrylate)-graft-poly(ethylene glycol). Polymerization was carried out using PEGMEMA-2000 as monomer and 5 mol% V-501 as initiator. PEGMEMA-2000 (0.6 g; 50 wt% in water, 0.15 mmol), 2.1 mg V-501 (0.0075 mmol) and 3 mL water were added to a Schlenk flask equipped with a magnetic stir bar. The flask was sealed and the solution was subjected to three freeze-pump-thaw cycles. The flask was placed in a preheated oil bath at 70 °C and the mixture was stirred at 400 rpm for 18 h. Homopolymer 1b was obtained by lyophilization.
[0120] Homopolymer 2a: Poly(methacryloyloxy)methylphosphonic acid). Polymerization was carried out using MMPA monomer, APS as initiator, and TEMED as base in a stoichiometric ratio of 1.0 / 0.5 / 2.3 equivalents. MMPA (0.3 g, 1.67 mmol), 193 mg of APS (0.846 mmol) and 33.3 mL of water were added to a Schlenk flask equipped with a magnetic stir bar. The flask was sealed and the solution was subjected to three freeze-pump-thaw cycles. TEMED (574 μL, 3.83 mmol) was added under positive argon pressure. The flask was resealed and the mixture was stirred at 400 rpm for 2 h at room temperature. Homopolymer 2a was obtained by lyophilization.
[0121] Homopolymer 2b: Poly(methacryloyloxy)methylphosphonic acid) 2b. Polymerization was carried out using MMPA monomer and 5 mol% V-501 as initiator. MMPA (0.3 g, 1.67 mmol), 23.3 mg V-501 (0.0831 mmol), and 0.6 mL water were added to a Schlenk flask equipped with a magnetic stir bar. The flask was sealed and the solution was subjected to three freeze-pump-thaw cycles. The flask was placed in a preheated oil bath at 70 °C and the mixture was stirred at 400 rpm for 104 h. Homopolymer 2b was obtained by lyophilization. [ka]
[0122] Copolymer 3a: Poly(methacryloyloxymethylphosphonic acid)-co-(methacrylate-graft-poly(ethylene oxide)). Polymerization was carried out using monomers PEGMEMA-300 and MMPA in a stoichiometric ratio of 3.0 / 1.0, and V-501 as initiator. PEGMEMA-300 (276 mg, 0.92 mmol), MMPA (55.8 mg, 0.31 mmol), V-501 (17.2 mg, 0.062 mmol) and 0.3 mL of methanol were added to a Schlenk flask equipped with a magnetic stir bar. The flask was sealed and the solution was subjected to three freeze-pump-thaw cycles. The flask was placed in a preheated oil bath at 70° C., and the mixture was stirred at 400 rpm for 72 h. Copolymer 3a was obtained by lyophilization.
[0123] Copolymer 3b: Poly(methacryloyloxymethylphosphonic acid)-co-(methacrylate-graft-poly(ethylene oxide)). Polymerization was carried out using monomers PEGMEMA-300 and MMPA in a stoichiometric ratio of 1.0 / 1.0, and V-501 as initiator. PEGMEMA-300 (186 mg, 0.62 mmol), MMPA (111.7 mg, 0.62 mmol), V-501 (17.4 mg, 0.062 mmol) and 0.3 mL of methanol were added to a Schlenk flask equipped with a magnetic stir bar. The flask was sealed and the solution was subjected to three freeze-pump-thaw cycles. The flask was placed in a preheated oil bath at 70° C., and the mixture was stirred at 400 rpm for 72 h. Copolymer 3b was obtained by lyophilization.
[0124] Copolymer 3c: Poly(methacryloyloxymethylphosphonic acid)-co-(methacrylate-graft-poly(ethylene oxide)). Polymerization was carried out using monomers PEGMEMA-300 and MMPA in a stoichiometric ratio of 1.0 / 3.0, and V-501 as initiator. PEGMEMA-300 (108 mg, 0.36 mmol), MMPA (192.7 mg, 1.07 mmol), V-501 (20.0 mg, 0.072 mmol) and 0.3 mL of methanol were added to a Schlenk flask equipped with a magnetic stir bar. The flask was sealed and the solution was subjected to three freeze-pump-thaw cycles. The flask was placed in a preheated oil bath at 70° C., and the mixture was stirred at 400 rpm for 72 h. Copolymer 3c was obtained by lyophilization.
[0125] Copolymer 3d: poly(methacryloyloxymethylphosphonic acid)-co-(methacrylate-graft-poly(ethylene oxide)). Polymerization was carried out using monomers PEGMEMA-500 and MMPA in a stoichiometric ratio of 3.0 / 1.0, with V-501 as the initiator. PEGMEMA-500 (267.8 mg, 0.54 mmol), MMPA (32.2 mg, 0.18 mmol), V-501 (10 mg, 0.034 mmol), 0.3 mL of methanol, and 0.3 mL of water were added to a Schlenk flask equipped with a magnetic stir bar. The flask was sealed and the volume above the solution was deoxygenated by purging with argon for 15 min, followed by bubbling argon through the solution for 5 min. The flask was placed in a preheated oil bath at 70 °C, and the mixture was stirred at 400 rpm for 72 h. Copolymer 3d was obtained by lyophilization.
[0126] Copolymer 3e: Poly(methacryloyloxymethylphosphonic acid)-co-(methacrylate-graft-poly(ethylene oxide)). Polymerization was carried out using monomers PEGMEMA-500 and MMPA in a stoichiometric ratio of 1.0 / 1.0, with V-501 as the initiator. PEGMEMA-500 (220.6 mg, 0.44 mmol), MMPA (79.4 mg, 0.44 mmol), V-501 (6.2 mg, 0.022 mmol), 0.3 mL of methanol, and 0.3 mL of water were added to a Schlenk flask equipped with a magnetic stir bar. The flask was sealed and the volume above the solution was deoxygenated by purging with argon for 15 min, followed by bubbling argon through the solution for 5 min. The flask was placed in a preheated oil bath at 70 °C, and the mixture was stirred at 400 rpm for 72 h. Copolymer 3e was obtained by lyophilization.
[0127] Copolymer 3f: Poly(methacryloyloxymethylphosphonic acid)-co-(methacrylate-graft-poly(ethylene oxide)). Polymerization was carried out using monomers PEGMEMA-500 and MMPA in a stoichiometric ratio of 1.0 / 3.0, with V-501 as the initiator. PEGMEMA-500 (144.2 mg, 0.29 mmol), MMPA (155.8 mg, 0.87 mmol), V-501 (8.1 mg, 0.029 mmol), 0.15 mL of methanol, and 0.15 mL of water were added to a Schlenk flask equipped with a magnetic stir bar. The flask was sealed and the volume above the solution was deoxygenated by purging with argon for 15 min, followed by bubbling argon through the solution for 5 min. The flask was placed in a preheated oil bath at 70 °C, and the mixture was stirred at 400 rpm for 24 h. Copolymer 3f was obtained by lyophilization.
[0128] Copolymer 3g: poly(methacryloyloxymethylphosphonic acid)-co-(methacrylate-graft-poly(ethylene oxide)). Polymerization was carried out using monomers PEGMEMA-950 and MMPA in a stoichiometric ratio of 3.0 / 1.0, with V-501 as initiator. PEGMEMA-950 (282.2 mg, 0.30 mmol), MMPA (17.8 mg, 0.099 mmol), V-501 (5.5 mg, 0.020 mmol), 0.8 mL of methanol, and 0.8 mL of water were added to a Schlenk flask equipped with a magnetic stir bar. The flask was sealed and the volume above the solution was deoxygenated by purging with argon for 15 min, followed by bubbling argon through the solution for 5 min. The flask was placed in a preheated oil bath at 70 °C, and the mixture was stirred at 400 rpm for 72 h. 3 g of copolymer was obtained by lyophilization.
[0129] Copolymer 3h: Poly(methacryloyloxymethylphosphonic acid)-co-(methacrylate-graft-poly(ethylene oxide)). Polymerization was carried out using monomers PEGMEMA-950 and MMPA in a stoichiometric ratio of 1.0 / 1.0, with V-501 as the initiator. PEGMEMA-950 (252.2 mg, 0.27 mmol), MMPA (47.8 mg, 0.27 mmol), V-501 (3.7 mg, 0.013 mmol), 0.8 mL of methanol, and 0.8 mL of water were added to a Schlenk flask equipped with a magnetic stir bar. The flask was sealed and the volume above the solution was deoxygenated by purging with argon for 15 min, followed by bubbling argon through the solution for 5 min. The flask was placed in a preheated oil bath at 70 °C, and the mixture was stirred at 400 rpm for 72 h. Copolymer 3h was obtained by lyophilization.
[0130] Copolymer 3i: Poly(methacryloyloxymethylphosphonic acid)-co-(methacrylate-graft-poly(ethylene oxide)). Polymerization was carried out using monomers PEGMEMA-950 and MMPA in a stoichiometric ratio of 1.0 / 3.0, with V-501 as the initiator. PEGMEMA-950 (191.2 mg, 0.20 mmol), MMPA (108.8 mg, 0.60 mmol), V-501 (5.6 mg, 0.020 mmol), 0.4 mL of methanol, and 0.4 mL of water were added to a Schlenk flask equipped with a magnetic stir bar. The flask was sealed and the volume above the solution was deoxygenated by purging with argon for 15 min, followed by bubbling argon through the solution for 5 min. The flask was placed in a preheated oil bath at 70 °C, and the mixture was stirred at 400 rpm for 24 h. Copolymer 3i was obtained by lyophilization.
[0131] Copolymer 3j: poly(methacryloyloxymethylphosphonic acid)-co-(methacrylate-graft-poly(ethylene oxide)). Polymerization was carried out using monomers PEGMEMA-2000 and MMPA in a stoichiometric ratio of 3.0 / 1.0, with 0.7 wt% V-501 as initiator. PEGMEMA-2000 (600 mg; 50 wt% in water, 0.15 mmol), 9 mg MMPA (0.05 mmol), 2.2 mg V-501 (0.0078 mmol) and 3 mL water were added to a Schlenk flask equipped with a magnetic stir bar. The flask was sealed and the solution was subjected to three freeze-pump-thaw cycles. The flask was placed in a preheated oil bath at 70 °C, and the mixture was stirred at 400 rpm for 80 h. Copolymer 3j was obtained by lyophilization.
[0132] Copolymer 3k: poly(methacryloyloxymethylphosphonic acid)-co-(methacrylate-graft-poly(ethylene oxide)). Polymerization was carried out using monomers PEGMEMA-2000 and MMPA in a stoichiometric ratio of 1.0 / 1.0, with 0.7 wt% V-501 as initiator. PEGMEMA-2000 (600 mg; 50 wt% aqueous solution, 0.15 mmol), 27 mg MMPA (0.15 mmol), 2.3 mg V-501 (0.0082 mmol) and 3 mL water were added to a Schlenk flask equipped with a magnetic stir bar. The flask was sealed and the solution was subjected to three freeze-pump-thaw cycles. The flask was placed in a preheated oil bath at 70° C. and the mixture was stirred at 400 rpm for 80 h. Copolymer 3k was obtained by lyophilization.
[0133] Copolymer 3l: poly(methacryloyloxymethylphosphonic acid)-co-(methacrylate-graft-poly(ethylene oxide)). Polymerization was carried out using monomers PEGMEMA-2000 and MMPA in a stoichiometric ratio of 1.0 / 3.0, with 0.7 wt% V-501 as initiator. PEGMEMA-2000 (600 mg; 50 wt% aqueous solution, 0.15 mmol), 81.1 mg MMPA (0.45 mmol), 2.7 mg V-501 (0.0096 mmol) and 3 mL water were added to a Schlenk flask equipped with a magnetic stir bar. The flask was sealed and the solution was subjected to three freeze-pump-thaw cycles. The flask was placed in a preheated oil bath at 70° C. and the mixture was stirred at 400 rpm for 80 h. Copolymer 3l was obtained by lyophilization.
[0134] Copolymer 3m: poly(methacryloyloxymethylphosphonic acid)-co-(methacrylate-graft-poly(ethylene oxide)). Polymerization was carried out using monomers PEGMEMA-2000 and MMPA, APS as initiator, and TEMED as base in a stoichiometric ratio of 3.0 / 1.0 / 2.0 / 9.2. PEGMEMA-2000 (583 mg, 50 wt% aqueous solution, 0.146 mmol), 8.7 mg MMPA (0.0485 mmol), 22.5 mg APS (0.0987 mmol), and 3.9 mL water were added to a Schlenk flask equipped with a magnetic stir bar. The flask was sealed and the solution was subjected to three freeze-pump-thaw cycles. TEMED (67 μL, 0.446 mmol) was then added under positive argon pressure. The flask was resealed and the mixture was stirred at 400 rpm for 2 h at room temperature. Copolymer 3m was obtained by freeze-drying.
[0135] Copolymer 3n: poly(methacryloyloxymethylphosphonic acid)-co-(methacrylate-graft-poly(ethylene oxide)). Polymerization was carried out using monomers PEGMEMA-2000 and MMPA, APS as initiator, and TEMED as base in a stoichiometric ratio of 1.0 / 1.0 / 1.0 / 4.6. PEGMEMA-2000 (550 mg, 50 wt% aqueous solution, 0.138 mmol), 24.8 mg MMPA (0.138 mmol), 31.9 mg APS (0.140 mmol), and 5.5 mL water were added to a Schlenk flask equipped with a magnetic stir bar. The flask was sealed and the solution was subjected to three freeze-pump-thaw cycles. TEMED (95 μL, 0.633 mmol) was added under positive argon pressure. The μ-flask was resealed and the mixture was stirred at 400 rpm for 2 h at room temperature. Copolymer 3n was obtained by freeze-drying.
[0136] Copolymer 3o: Poly(methacryloyloxymethylphosphonic acid)-co-(methacrylate-graft-poly(ethylene oxide)). Polymerization was carried out using monomers PEGMEMA-2000 and MMPA, APS as initiator, and TEMED as base in a stoichiometric ratio of 1.0 / 3.0 / 2.0 / 9.2. PEGMEMA-2000 (472 mg, 50 wt% aqueous solution, 0.118 mmol), 63.8 mg MMPA (0.354 mmol), 54.8 mg APS (0.240 mmol), and 9.4 mL water were added to a Schlenk flask equipped with a magnetic stir bar. The flask was sealed and the solution was subjected to three freeze-pump-thaw cycles. TEMED (162.8 μL, 1.09 mmol) was then added under positive argon pressure. The μ-flask was resealed and the mixture was stirred at 400 rpm for 2 h at room temperature. Copolymer 3o was obtained by freeze-drying.
[0137] Copolymer 4: Poly(hydroxyethyl methacrylate)-co-(methacryloyloxymethylphosphonic acid). Polymerization was carried out using monomers HEMA and MMPA in a stoichiometric ratio of 3.0 / 1.0, with 5 mol% of V-501 as initiator. HEMA (300 mg, 2.31 mmol), 136 mg of MMPA (0.77 mmol), 41.3 mg of V-501 (0.147 mmol), and 2 mL of methanol were added to a Schlenk flask equipped with a magnetic stir bar. The flask was sealed and deoxygenated by purging with argon for 15 min, followed by bubbling argon through the solution for 5 min. The flask was placed in a preheated oil bath at 70 °C, and the mixture was stirred at 400 rpm for 72 h. Copolymer 4 was obtained by precipitation into n-hexane. [ka]
[0138] Copolymer 5: Poly(2-methacryloyloxyethyl phosphorylcholine)-co-(methacryloyloxymethylphosphonic acid). Polymerization was carried out using monomers MPC and MMPA in a stoichiometric ratio of 3.0 / 1.0, with 5 mol% of V-501 as initiator. MPC (300 mg, 1.02 mmol), 61 mg of MMPA (0.339 mmol), 19 mg of V-501 (0.068 mmol), and 0.8 mL of methanol were added to a Schlenk flask equipped with a magnetic stir bar. The flask was sealed and deoxygenated by purging with argon for 15 min, followed by bubbling argon through the solution for 5 min. The flask was placed in a preheated oil bath at 70 °C, and the mixture was stirred at 400 rpm for 72 h. Copolymer 5 was obtained by precipitation into acetone.
[0139] Copolymer 6: Poly(2,2,2-trifluoroethyl methacrylate)-co-(methacryloyloxymethylphosphonic acid). Polymerization was carried out using monomers TFEMA and MMPA in a stoichiometric ratio of 3.0 / 1.0, with 5 mol% of V-501 as initiator. TFEMA (300 mg, 1.78 mmol), 107 mg of MMPA (0.595 mmol), 33.3 mg of V-501 (0.119 mmol), and 0.8 mL of methanol were added to a Schlenk flask equipped with a magnetic stir bar. The flask was sealed and deoxygenated by purging with argon for 15 min, followed by bubbling argon through the solution for 5 min. The flask was placed in a preheated oil bath at 70 °C, and the mixture was stirred at 400 rpm for 72 h. Copolymer 6 was obtained by precipitation into n-hexane. [ka]
[0140] Copolymer 7: Poly(butyl methacrylate)-co-(methacryloyloxymethylphosphonic acid). Polymerization was carried out using monomers BMA and MMPA in a stoichiometric ratio of 3.0 / 1.0, with 5 mol% of V-501 as initiator. BMA (300 mg, 2.10 mmol), 126.7 mg of MMPA (0.703 mmol), 39.3 mg of V-501 (0.140 mmol), 0.4 mL of isopropanol, and 0.6 mL of methanol were added to a Schlenk flask equipped with a magnetic stir bar. The flask was sealed and deoxygenated by purging with argon for 15 min, followed by bubbling argon through the solution for 5 min. The flask was placed in a preheated oil bath at 70 °C, and the mixture was stirred at 400 rpm for 72 h. Copolymer 7 was obtained by precipitation into methanol / water (1:1 (v / v)).
[0141] Example 2: Coating of metal articles with a pretreatment solution Analytical instruments and methods: Water contact angle measurements. Water contact angles were measured using a DataPhysics OCA35 water contact angle measurement system (Dataphysics, San Jose, CA, USA). Water and lubricant droplets (1 μL each) were deposited on the substrate and allowed to equilibrate for 10 s. Contact angles were calculated from the droplet shape using the Young-Laplace equation.
[0142] Ellipsometry of dry film thickness. Dry film thickness was measured using a variable angle spectroscopic ellipsometer (Semilab SE2000, Semilab ZRt, Budapest, Hungary). Ellipsometry data were recorded at angles of incidence of 65°, 70°, and 75° using a wavelength range of 245 nm to 990 nm. The ellipsometry data, angles Ψ and Δ were analyzed using the software provided with the instrument (Spectroscopic Ellipsometry Analyzer v1.6.1 (Semilab)). The calculation method was based on a five-layer silicon / silicon oxide / aluminum oxide / polymer brush / polymer brush / ambient model, which assumes that the polymer brush layer is isotropic and uniform. The refractive index (n) of the polymer brush layer was calculated using the Cauchy approximation (n=A n +B n / λ 2 ) and the layer thicknesses were fitted by the software. All reported ellipsometric film thicknesses on silicon wafers are corrected for an approximately 1.5 nm thick native oxide layer on the silicon wafer and a 10 nm aluminum oxide layer grown by atomic layer deposition (ALD).
[0143] Atomic force microscopy (AFM). AFM imaging was performed in tapping mode (AC Air topography mode) using HQ-NSC18 / Al BS silicon cantilevers (resonant frequencies f = 60–90 kHz, force constants k = 1.2–5.5 N / m) on a Cypher VRS platform (Asylum Research, Oxford Instruments, Oxford, UK). The cantilever vibration was driven by photothermal excitation. The analyzed area was 2 μm × 2 μm using a scan rate of 2.5 Hz.
[0144] Friction analysis using nanotribometer. TTX, STeP - NTR 3 The instrument (Nano Tribometer, Anton Paar GmbH, Graz, Austria) and the ST-S (maximum normal load and friction load, F n , F t =100mN) or HL-S (max F n , F t =1N) cantilevers were used for friction measurements. Nanotribology tests were performed on polymer-coated silicon / alumina wafers using a 2 mm diameter steel 100Cr6 ball at loads of 1, 10, 100 (using ST-S cantilever), and 300 mN (using HL-S cantilever). The sliding distance was 2 mm at 0.8 Hz (maximum linear speed 5 mm / s) over 500 cycles. No additional lubricant was used.
[0145] Coating Procedure: Spin coating was performed to evaluate the graft copolymer coating applied to an aluminum oxide layer on a silicon wafer as a model substrate. The spin-coated substrate (e.g., aluminum oxide coated silicon wafer, or wafer) was sonicated in acetone and isopropanol for 5 min, respectively. The wafer was then rinsed with isopropanol and blown dry with argon. The wafer was then placed in an oxygen plasma generator that supplied 92 W of energy for 5 min under an oxygen flow of 10 mL / min. The cleaned wafer was spin-coated with 10 μL of 2 wt%, 5 wt%, and 10 wt% homopolymer aqueous solutions 2a. Spin coating was performed at 1000 rpm and 2000 rpm for 5 min, and 4000 rpm and 8000 rpm for 1 min to evaluate the spin coating properties. The coated wafer was then placed on a heating stage preheated to 70 °C and dried for 2 h. The samples were stored under ambient atmosphere and analyzed by water contact angle measurements and spectroscopic ellipsometry. The thickness range for the 2 wt % spin-cast solutions was 5-15 nm, the thickness range for the 5 wt % spin-cast solutions was 20-55 nm, and the thickness range for the 10 wt % spin-cast solutions was 35-95 nm. Ellipsometry measurements were performed within one week after coating.
[0146] Figure 1 shows the dry polymer film thickness as a function of spin-coating speed (referred to as "w" in Figure 1 in rpm) for three solutions of homopolymer 2a in water at concentrations of 2 wt%, 5 wt%, and 10 wt%. The film thickness scales well with the theoretical dependence shown by the dashed line (i.e., film thickness scales with the inverse square root of the spin speed, d = A w (-1 / 2) , where d is the film thickness, w is the spin speed, and A is the spin duration.
[0147] Copolymers 3j, 3k, and 3l were spin-coated onto aluminum oxide layers on silicon wafers to evaluate film thickness. Wafers cleaned as above were spin-coated with 10 μL of 2 wt % aqueous solutions of copolymers 3j, 3k, and 3l at 2000 rpm for 5 min and at 4000 rpm and 8000 rpm for 1 min. The coated wafers were then placed on a heating stage preheated to 70 °C and dried for 2 h. The samples were stored under ambient atmosphere and analyzed by water contact angle measurements, spectroscopic ellipsometry, and atomic force microscopy. The thicknesses of the spin-cast solutions ranged from 5.3 nm to 8.2 nm at 2000 rpm, 14.9 nm to 48.3 nm at 4000 rpm, and 15.2 nm to 35.9 nm at 8000 rpm. These values were similar to those obtained from atomic force microscopy step analysis, in which part of the copolymer coating was removed by scratching with a sharp steel needle (see Figures 2 and 3). Figure 2 shows AFM images of substrates spin-coated with 2 wt% copolymer 3j in water. The cross section shows a copolymer coating between 33.7 nm and 43.6 nm thick. Figure 3 shows AFM images of substrates spin-coated with 2 wt% copolymer 3j in water and subsequently washed with water. The cross section shows a copolymer coating between 8.8 nm and 9.3 nm thick.
[0148] Copolymers 3a, 4, 5, 6, and 7 were spin-coated onto aluminum oxide layers on silicon wafers to evaluate film thickness. Cleaned wafers were spin-coated with 50 μL of 2 wt % aqueous solutions of polymers 3a, 4, 5, 6, and 7 at 8000 rpm for 1 min. The coated wafers were then placed on a heating stage preheated to 70° C. and allowed to dry for 10 min. The samples were stored under ambient atmosphere and the thickness of the polymer coating was evaluated by spectroscopic ellipsometry as shown in Table 1 below. [Table 1]
[0149] Additionally, copolymers 3a, 4, 5, 6, and 7 were spin-coated at 8000 rpm for 1 min onto cleaned aluminum oxide layers on silicon wafers. The coated wafers were then placed on a heating stage preheated to 70° C. and dried for 10 min. The samples were then immersed in either water (copolymers 3a, 4, and 5) or isopropanol (copolymers 6 and 7) for 15 min, followed by rinsing with the respective solvent, then with isopropanol, and blow-drying with argon. The samples were stored under ambient atmosphere and the film thickness was evaluated by spectroscopic ellipsometry, as shown in Table 2 below. [Table 2]
[0150] Copolymers 3a, 3b, and 3c, spin-coated onto an aluminum oxide layer on a silicon wafer, were analyzed by X-ray photoelectron spectroscopy (XPS) using C 1s, P 2s, and P 2p high-resolution scans to confirm the presence of the copolymers. Figures 4-6 show X-ray photoelectron spectroscopy scans of copolymer 3a (Figure 4), copolymer 3b (Figure 5), and copolymer 3c (Figure 6) films. The deconvoluted C 1s scans (left graphs in each of Figures 4-6) show the presence of aliphatic carbon atoms (signal at 285 eV), carbon atoms of the PEG chains (signal at 286.3 eV), and carbonyl atoms belonging to the methacrylate groups of the polymer backbone (signal at 289 eV). The phosphorus scans show peaks at 191 eV in the P 2s scan and 134 eV in the P 2p scan. The intensity of the phosphorus scans in both the P 2s region (middle graphs in each of Figures 4-6) and the P 2p region (right graphs in each of Figures 4-6) is well proportional to the increasing amount of phosphonic acid in the copolymer samples (i.e., the P signal of copolymer 3b is doubled compared to copolymer 3a, and the P signal of copolymer 3c is tripled compared to copolymer 3a).
[0151] The film thickness of the polymer gel layer was evaluated by spin-coating copolymer 3h onto an aluminum oxide layer on a silicon wafer. Wafers cleaned as above were spin-coated with 40 μL of a 2 wt % solution of copolymer 3h in a 9:1 methanol-water mixture at 2500, 5000, 7000, and 8000 rpm for 1 min. The silicon wafer was then incubated in a 5 mM solution of zirconium bis(acetylacetonate) in ethanol for 1 h. The zirconium ions crosslink the phosphonic acid functional groups in the copolymer, forming a polymer gel layer. After rinsing with ethanol, the silicon wafer was spin-dried at 8000 rpm for 30 s. The resulting film thicknesses, determined by ellipsometry, were 58.6 ± 1.9 nm at 2500 rpm, 42.5 ± 1.2 at 5000 rpm, 38.8 ± 1.4 nm at 7000 rpm, and 38.1 ± 1.4 at 8000 rpm, respectively.
[0152] Copolymer 3h was spin-coated onto an aluminum oxide layer on a silicon wafer, and the 5754 aluminum sample was pretreated with EDT, a tetrahydroacridine derivative (e.g., 5754 EDT aluminum), as described above, for 1 min at 8000 rpm. The thickness of the polymer layer was controlled by varying the polymer concentration in the spin-coating solution from 0.38 wt% to 3.0 wt% in a methanol-water mixture (9:1). After spin-coating, the sample was incubated for 1 h in a 5 mM solution of zirconium bis(acetylacetonate) in ethanol for cross-linking. The sample was rinsed with ethanol and spin-dried at 8000 rpm for 10 s. Figure 7 and Table 3 show how the thickness of the gel layer correlates with the polymer concentration in the spin-coating process. The thickness of the polymer gel layer can be controlled by the polymer concentration in the spin-coating process. Figure 8 is a schematic diagram of the polymer gel layer. Figure 9 and Table 4 show the XPS data before (Figure 9, top panel) and after (Figure 9, bottom panel) crosslinking (referred to as "zirconization" in Figure 9), indicating the presence of zirconium crosslinks. [Table 3] [Table 4]
[0153] Crosslinking of spin-coated layers of copolymer 3h by zirconium ions is typically achieved by incubation for up to 15 min at concentrations in the mM range at room temperature. For zirconium concentrations in the submillimeter range, the thickness of the polymer gel layer is significantly reduced after rinsing, indicating that crosslinking is not achieved to a sufficient degree to form a structurally stable polymer gel layer. The reduction in the thickness of the polymer gel layer is also reflected in the reduction in sliding distance in nanotribology experiments. Increasing the concentration does not further improve the stability of the polymer gel layer (Figure 10 and Table 5). After incubation for 1 min at room temperature in a 5 mM zirconium bis(acetylacetonate) (Zr(acac)4) solution in ethanol, a stable polymer gel layer is formed. XPS data show that crosslinking is complete after up to 15 min (Figure 11 and Table 6). No significant increase in zirconium content was observed with longer incubation times. For the non-crosslinked comparative sample, a significant decrease in the thickness of the polymer layer was observed after rinsing, indicating that without crosslinking the zirconium ions, a significant amount of polymer is removed from the surface during the rinsing step. [Table 5] [Table 6]
[0154] Crosslinking with zirconium bis(acetylacetonate) can also be achieved by immersion in aqueous solutions. Figure 19 shows the tribological performance at a force of 300 mN normal load of a polymer gel layer prepared by crosslinking a 239 nm copolymer 3h layer spin-coated onto 5457EDT aluminum in 5 mM solutions of zirconium bis(acetylacetonate) in ethanol, in water at pH 6.19, and in a weakly acidic aqueous solution at pH 4.56, respectively. In the latter solution, a small amount of sulfuric acid was added to lower the pH. The lower pH promotes the solubility and stability of zirconium bis(acetylacetonate) in aqueous solutions, as shown by the improved tribological performance of the corresponding polymer gel modified surfaces. The decomposition products form precipitates on the surface, which can lead to an increase in the initial friction coefficient and a decrease in the sliding distance, as observed for the polymer gel prepared in water at pH 6.19. Application from aqueous solutions is an important environmental and economic factor.
[0155] Example 3: Coating properties The homopolymer 2a films were analyzed by nanotribology to determine the coefficient of friction of the coated surfaces. Using the method described above, nanotribology tests were performed on aluminum oxide layers on silicon wafers coated with homopolymer 2a. Nanotribology tests were performed at forces of 100 mN, 10 mN, and 1 mN. Figure 12 shows the nanotribology results of wafers coated with 4.6 nm thick films and 2.3 nm thick films. The 4.6 nm thick films and the 2.3 nm thick films were tested for 500 cycles at a force of 100 mN. As shown in Figure 12, both the 4.6 nm thick film and the 2.3 nm thick film obtained a friction coefficient (μ) of about 0.7, which remained constant over 500 cycles. Figure 13 shows the nanotribology results of wafers coated with 30.6 nm thick films. The 30.6 nm thick film was tested for 500 cycles at a force of 10 mN. As shown in FIG. 13, the 30.6 nm thick film exhibited an unstable coefficient of friction over 500 cycles. FIG. 14 is a graph comparing the nanotribology results of wafers coated with 30.6 nm, 4.6 nm, and 2.3 nm thick films. The 30.6 nm, 4.6 nm, and 2.3 nm thick films were tested for 500 cycles at a force of 1 mN. The 4.6 nm and 2.3 nm thick films exhibited lower coefficients of friction and higher stability compared to the thicker 30.6 nm film. As shown in FIG. 14, both the 4.6 nm and 2.3 nm thick films exhibited friction coefficients less than about μ=0.4 and were constant over 500 cycles, while the 30.6 nm thick film exhibited a higher and more unstable coefficient of friction over 500 cycles.
[0156] Copolymer 3a, 4, 5, 6 and 7 films were analyzed by nanotribology to determine the coefficient of friction of the coated surfaces and the maximum sliding distance of the initial coefficient of friction. Using the method described above, nanotribology tests were performed on aluminum oxide layers on silicon wafers coated with copolymer 3a, copolymer 4, copolymer 5, copolymer 6 and copolymer 7. Nanotribology tests were performed at forces of 300 mN (Figures 15 and 17) and 100 mN (Figures 16 and 18). All of these tests show that the surface has an initially low coefficient of friction that then increases rapidly, indicating mechanical damage to the coating.
[0157] Figures 15 and 16 show the performance of spin-coated films with thicknesses between 24 nm and 71 nm. Figures 17 and 18 show the performance of spin-coated films with thicknesses between 24 nm and 71 nm that were further subjected to a washing step to remove unbound and / or excess copolymer material. Under both 300 mN and 100 mN forces, the films containing copolymer 3a show lower initial friction coefficients of 0.15 for tests performed at 300 mN and 0.2 for tests performed at the normal load of 100 mN. Similarly, the copolymer 3a films maintain the lowest friction coefficients over longer sliding distances of 43 cm for tests performed at 100 mN and 10 cm for tests performed at 300 mN load for spin-coated films. These results show surprisingly good performance of the copolymers described herein, given the film thicknesses on the order of nanometers and the absence of additional lubricants. Films containing copolymers without PEG chains grafted thereon consistently performed worse. After washing off the excess copolymer, the tests (see Figures 17 and 18) have little effect on the minimum friction coefficient. In the 100 mN test (see Figure 17), the maximum sliding distance decreases from 43 cm to about 23 cm for the copolymer 3a film. In contrast, in the 300 mN test (see Figure 18), this distance does not decrease. Surprisingly, at 300 mN, the thicker coating seems to play little role and the performance is determined only by the more firmly bonded layer.
[0158] The water contact angle (labeled "WCA" in FIG. 24) and lubricant AL200 contact angle (labeled "AL200 CA" in FIG. 24) measurements for copolymer 3a (labeled "PEGMEMA300-MMPA" in FIG. 24), 4 (labeled "HEMA-MMPA" in FIG. 24), 5 (labeled "MPC-MMPA" in FIG. 24), 6 (labeled "FEMA-MMPA" in FIG. 24), and 7 (labeled "BMA-MMPA" in FIG. 24) films were measured and a comparison is shown in FIG. 24. The water contact angle for copolymer 3a was approximately 60°. For copolymer 5, which contains a highly polar zwitterionic comonomer component, a water contact angle of about 42° was observed.
[0159] Copolymer 3a films with a coating of 9.66 nm were lubricated by spin coating with a 1 wt% solution of AL200 in isopropanol at 8000 rpm for 1 min. The thickness of the lubricated surface was about 54 nm as assessed by spectroscopic ellipsometry. In addition, a reference substrate without any polymer coating was lubricated in a similar manner. The lubricated samples were analyzed by nanotribology to determine the coefficient of friction of the coated surfaces and the maximum sliding distance of the initial coefficient of friction (see Figures 25 and 26). Nanotribology tests were performed at forces of 100 mN (left graphs in Figures 25 and 26, respectively), 300 mN (second from the left graphs in Figures 25 and 26, respectively), 600 mN (third from the left graphs in Figures 25 and 26, respectively), and 1000 mN (right graphs in Figures 25 and 26, respectively). For all samples, the initial coefficient of friction is about 0.1. After a certain sliding distance, the friction coefficient increases rapidly to about 0.7, indicating that the AL200 lubricant has been removed. This maximum sliding distance at low friction coefficient is generally much larger for the copolymer 3a film. For example, at 100 mN, the sliding distance increases from 600-800 cm to over 1200 cm; at 300 mN, it increases from 100 cm to over 600 cm; at 600 mN, no increase is observed; at 1000 mN, it increases from 0-50 cm to 200-230 cm.
[0160] Copolymer 3a, 3b, 3c, 3d, 3e, 3h, and 3k films were analyzed by nanotribology to systematically study the influence of chemical structure features such as PEG chain length and density of phosphonic acid anchor groups on the performance of the coatings. Nanotribological tests were performed at forces of 300 mN (Figures 27 and 29) and 100 mN (Figures 28 and 30).
[0161] Figures 27 and 28 show the tribological performance of copolymer 3a (left column in Figures 27-28), 3b (middle column in Figures 27-28), and 3c (right column in Figures 27-28) films consisting of copolymer chains synthesized using PEGMEMA-300 and increasing amounts of MMPA (at molar ratios of 3:1, 1:1, and 1:3). These films provided only moderate lubrication, as the initial friction coefficients for these substrates exceeded 0.3 when tested under a normal load of 100 mN. Furthermore, the maximum sliding distances at these low friction coefficients were mostly less than 10 cm. Increasing the amount of phosphonic methacrylate bonded in the copolymer chains did not improve these distances, but rather reduced the performance, as the initial friction coefficient increased from 0.3 for the lowest phosphonic acid content to 0.5 for the highest phosphonic acid content. These effects were slightly lower during testing under a higher load of 300 mN (e.g., the initial friction coefficient increased from 0.2 for the lowest phosphonic acid content to 0.4 for the highest phosphonic acid content, and the maximum sliding distance was only slightly affected).
[0162] Figures 29 and 30 show the tribological performance of copolymers 3d (left column in Figures 29-30) and 3e (second from the left column in Figures 29-30), which were synthesized using monomers PEGMEMA-500 and MMPA (molar ratios 3:1 and 1:1). Surprisingly, copolymers 3d and 3e showed a clear improvement in the maximum sliding distance at the initial friction coefficient when the amount of phosphonic acid anchor groups was increased to 50 mol%. The maximum sliding distance increased from about 10 cm to 25 cm for the spin-coated samples. Copolymers 3h (third from the left column in Figures 29-30) and 3k (right column in Figures 29-30) were synthesized using monomers PEGMEMA-950 and PEGMEMA-2000, respectively. Copolymer 3h film showed a similar maximum sliding distance compared to copolymers 3d and 3e, but a lower initial friction coefficient of 0.1 compared to 0.2 for copolymer 3e film. For the spin-coated samples, further increasing the length of the PEG chain does not lead to any further improvement, as the initial friction coefficient remains around 0.1 and the maximum sliding distance decreases from 20 to 10 cm.
[0163] Figure 21 shows the tribological performance of zirconium crosslinked polymer gel films of copolymer 3h with thicknesses applied by roll coating from aqueous polymer solutions. A 5754EDT aluminum sheet of size 210 x 297 mm (A4) was coated. The sheet was dried at 35 °C for 5 min and subsequently incubated at room temperature in a solution of 5 mM zirconium bis(acetylacetonate) in ethanol for 1 h. Zirconium crosslinked polymer gel films of copolymer 3h with thicknesses between 16.5 nm and 147 nm were obtained using polymer concentrations of 2.22, 1.11, 0.55 and 0.28 wt% in water. Before performing nanotribological measurements, the sheet was rinsed with ethanol and dried at room temperature. A force of normal load of 300 mN was applied to the film. This example shows that application of polymers from aqueous solutions is possible using techniques commonly used in large-scale production. Figure 21 shows the tribological performance under normal load of 300 mN. The films exhibit an initial coefficient of friction (COF, μ) <0.2. The sliding distances range from 11.7 cm for a 16.5 nm thick polymer gel layer to 71 cm for a 128 nm thick polymer gel layer. These results indicate good lubrication performance of the copolymer gels described herein, given the film thickness in the nanometer range and the absence of additional lubricants.
[0164] The storage stability of the polymer gels prepared from copolymer 3h was investigated under the following conditions: up to 72 hours in a freeze dryer, up to 64 hours in an oven at 60 °C, and up to 1 month under ambient conditions (Figure 23). The thickness of the polymer gel layer during storage was monitored by ellipsometry using silicon wafers coated with aluminum oxide as substrate, and by tribological performance using 5754EDT aluminum as substrate with a normal load force of 300 mN. As is evident from Figure 23, the tribological performance did not decrease significantly when stored under ambient conditions, and was not impaired even in the high vacuum conditions of the freeze dryer up to 72 °C. Storage at higher temperatures, e.g., at 60 °C for 64 hours in an oven, results in a decrease in tribological performance after more than 1 hour of incubation. The lubricating properties are lost after 64 hours of incubation. The samples were not rewetted or otherwise treated before tribological measurements. The presented data indicate an advantageous storage stability of the polymer gels.
[0165] By repeating the spin-coating and cross-linking steps several times, a laminated structure can be obtained. Copolymer 3h was spin-coated onto an aluminum oxide-coated silicon wafer and subsequently cross-linked by incubation in a 5 mM zirconium bis(acetylacetonate) solution in ethanol. This two-step procedure was repeated up to two more times. Figure 22 shows the nanotribological performance after one (second panel from the left), two (third panel from the left), and three (right-most panel) applications, applying a normal load of 300 mN.
[0166] All patents, patent specifications, publications, and abstracts cited above are incorporated herein by reference in their entirety. Reference has been made in detail to various embodiments of the disclosed subject matter, one or more examples of which are described above. Each example is provided as an explanation of the subject matter, and not as a limitation of the subject matter. Indeed, it will be apparent to those skilled in the art that various modifications and variations can be made in the present disclosure without departing from the scope or spirit of the subject matter. For example, features illustrated or described as part of one embodiment may be used with another embodiment to yield still a further embodiment.
Claims
1. Polymer backbone; at least one surface bonding or joining moiety attached to the polymer backbone and configured to bond or join the polymer backbone to a first surface of a metal article; at least one functional moiety attached to the polymer backbone and configured to provide at least a first surface functionalization to the first surface of the metal article; and at least one second functional moiety attached to the polymer backbone and configured to provide at least a second surface functionalization to the first surface of the metal article; wherein the at least one functional portion and the at least one second functional portion provide a multi-functional surface coating.
2. 10. The graft copolymer pretreatment composition of claim 1, wherein the polymer backbone comprises a linear polymer structure of the acrylic class, a linear polymer structure of the methacrylic class, a linear polymer structure of the vinyl class, a linear polymer structure of the diene class, a linear polymer structure of the vinylidene class, or any combination thereof.
3. 3. The graft copolymer pretreatment composition of claim 1 or 2, wherein the polymer backbone is poly(methyl methacrylate), poly(ethyl methacrylate), poly(ethyl acrylate), polyacrylonitrile, polyethylene, polypropylene, polystyrene, poly(vinyl chloride), poly(vinyl acetate), poly(vinyl alcohol), polybutadiene, polyisoprene, polychloroprene, or any combination thereof.
4. The graft copolymer pretreatment composition of any one of claims 1 to 3, wherein the at least one surface-bonding or bonding moiety comprises a phosphonate group, a carboxyl group, a catechol group, or a trialkoxysilyl group.
5. The graft copolymer pretreatment composition of claim 4 , wherein the phosphonate group comprises a poly(vinyl phosphonate).
6. The graft copolymer pretreatment composition of any one of claims 1 to 5, wherein the at least one functional moiety comprises an adhesion promoter.
7. 7. The graft copolymer pretreatment composition of claim 6, wherein the adhesion promoter comprises a hydroxyl group, an amide group, a thiol group, an epoxide group, a vinyl group, a diol group, an adhesive composition, a covalent bonding group, or an ionic bonding group.
8. The graft copolymer pretreatment composition of any one of claims 1 to 7, wherein the at least one functional moiety comprises a polymeric side chain that provides a lubricating function.
9. 9. The graft copolymer pretreatment composition of claim 8, wherein the polymer side chains that provide a lubricating function comprise polyethylene glycol, polytetrahydrofuran, polyisobutene, polysilicone, or any combination thereof.
10. The graft copolymer pretreatment composition of any one of claims 1 to 9, wherein the at least one functional moiety comprises a humectant.
11. 11. The graft copolymer pretreatment composition of claim 10, wherein the humectant comprises polypropylene glycol, hexylene glycol, butylene glycol, lactic acid, sodium hexametaphosphate, glycerol, sorbitol, xylitol, maltitol, urea, or any combination thereof.
12. The graft copolymer pretreatment composition of any one of claims 1 to 11, wherein the at least one functional moiety comprises a welding promoter.
13. The graft copolymer pretreatment composition of any one of claims 1 to 12, wherein the at least one functional moiety comprises a corrosion inhibitor.
14. 14. The graft copolymer pretreatment composition of claim 13, wherein the corrosion inhibitor comprises an inorganic corrosion inhibitor, an inorganic barrier type corrosion inhibitor, an organic corrosion inhibitor, an organic barrier type corrosion inhibitor, or any combination thereof.
15. 15. The graft copolymer pretreatment composition of claim 14, wherein the corrosion inhibitor comprises an inorganic corrosion inhibitor, the inorganic corrosion inhibitor comprising a transition metal, a transition metal salt, a rare earth metal, or a rare earth metal salt.
16. 16. The graft copolymer pretreatment composition of claim 15, wherein the inorganic corrosion inhibitor comprises a transition metal, the transition metal comprising titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), zirconium (Zr), niobium (Nb), molybdenum (Mo), ruthenium (Ru), rhodium (Rh), palladium (Pd), silver (Ag), cadmium (Cd), hafnium (Hf), tantalum (Ta), tungsten (W), rhenium (Re), osmium (Os), iridium (Ir), platinum (Pt), or gold (Au).
17. 16. The graft copolymer pretreatment composition of claim 15, wherein the inorganic corrosion inhibitor comprises a transition metal salt, the transition metal salt comprising a salt of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Cd, Hf, Ta, W, Re, Os, Ir, Pt, or Au.
18. 16. The graft copolymer pretreatment composition of claim 15, wherein the inorganic corrosion inhibitor comprises a rare earth metal, the rare earth metal comprising cerium (Ce), scandium (Sc), yttrium (Y), lanthanum (La), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), or lutetium (Lu).
19. 16. The graft copolymer pretreatment composition of claim 15, wherein the inorganic corrosion inhibitor comprises a rare earth metal salt, the rare earth metal salt comprising a salt of Ce, Sc, Y, La, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, or Lu.
20. 15. The graft copolymer pretreatment composition of claim 14, wherein the corrosion inhibitor comprises an organic corrosion inhibitor, the organic corrosion inhibitor comprising mercaptobenzothiazole, benzotriazole, salicylaldoxime, dithiooxamide, quinaldic acid, thioacetamide, or 8-hydroxyquinoline.
21. 21. The graft copolymer pretreatment composition of any one of claims 1 to 20, wherein the at least one second functional moiety comprises an adhesion promoter, a polymeric side chain providing a lubricating function, a humectant, a welding promoter, or a corrosion inhibitor.
22. The graft copolymer pretreatment composition of any one of claims 1 to 21, wherein the graft copolymer pretreatment composition is crosslinked with a crosslinking agent.
23. 23. The graft copolymer pretreatment composition of claim 22, wherein the crosslinking agent is a zirconium salt or a zirconium complex.
24. 24. The graft copolymer pretreatment composition of claim 22 or 23, wherein the crosslinking agent is an aqueous solution of a zirconium salt or zirconium complex.
25. 1. A method for pre-treating at least a portion of a metal surface, comprising the steps of: The method of claim 1, further comprising applying a graft copolymer pretreatment composition according to any one of claims 1 to 24 to at least a portion of the metal surface.
26. 26. The method of claim 25, wherein applying the graft copolymer pretreatment composition comprises solution coating at least a portion of the metal surface.
27. 27. The method of claim 26, wherein the solution coating comprises roll coating, dip coating, enrobing, spin coating, or spray coating at least a portion of the metal surface.
Citation Information
Patent Citations
Resin for coating and adhesion of metal
JP1992080277A
Surface treating agent for galvanized steel sheet, and surface treated galvanized steel sheet
JP2000178761A
Surface treating agent and surface treated steel sheet
JP2000219974A
Coating of aluminum alloy substrates
JP2003513773A
Methods and formulations for passivating metal surfaces using copolymers containing phosphate and / or phosphonate groups
JP2009544847A